Covalent coupling of myofibrillar protein–6-gingerol: Binding sites, alterations in protein structure and gel properties - Jiamei Li; Geyi Ren; Jiaqi Sun; Fei Li; Hongzhao Zhang; Ping Han; Shiling Lu; Juan Dong (Journal of Food Engineering, 2027)

Experimental and numerical studies of the effect of local heating on hydrogen dispersion in confined spaces - Zilong Zhang; Shengqi Lyu; Yuqi Zhou; Xinmeng Zhang; Jiangtao Sun; Yujie Ouyang; Zhaotong Zhang; Juan Mei; Hongyan Wang; Jing Zhang; Bin Li; Lifeng Xie (Fuel, 2027)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

Correction: Molecular mechanisms of UCP1-independent thermogenesis: the role of futile cycles in energy dissipation - Quanhao Sun; Xinyue Cui; Dong Yin; Juan Li; Jiarui Li; Likun Du (Journal of Physiology and Biochemistry, 2026)

Current Advances in Microbial Degradation for Fluoroquinolones: Degraders, Mechanisms and Applications - Tongtong Liu; Qin Ding; Yuan Hong; Zhuoxiao Li; Rongli Sun; Juan Zhang (Reviews of Environmental Contamination and Toxicology, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

PRMT5 lactylation mediates SIRT6-dependent DNA damage and senescence in benzene-induced hematotoxicity - Rongli Sun; Kai Xu; Xiaoqin Li; Jiawei Huang; Daqin Wang; Yuepu Pu; Juan Zhang (Food and Chemical Toxicology, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

High-precision semantic segmentation of apple internal diseases based on CT imaging and deep learning - Linfeng Su; Zhanling Hu; Ziqi Li; Jiacheng Sun; Juan Zhao (Postharvest Biology and Technology, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Synergistic reinforcement of carboxymethyl cellulose film with deep eutectic extract and polydopamine@nanolignin from spent coffee grounds: Enhanced antioxidant and photothermal antibacterial activity for active food packaging - Junxian Yang; Fangfei Sun; Juan Zhao; Wenhui Zhao; Hui Li; Lincai Peng (Food Research International, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Hazard identification of pathogenic microorganisms carried by ballast water of inbound ships in Qingdao Port, 2023-2024 - Jiansen Du; Jiawei Li; Yingquan Yu; Di Liu; Tao Zhang; Jin Zhang; Juan Zhang; Yan Sun; Hefei Xu (Estuarine, Coastal and Shelf Science, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Chemical constituents from the root of Bistorta suffulta (Maxim.) H. Gross and their chemotaxonomic significance - Xin-Yi Liu; Chun-Yi Li; Meng-Yin Luo; Xu Yang; Lu-Jun Li; Li-Juan Sun; Chun-Yang Shi (Biochemical Systematics and Ecology, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Tamarind shell extract alleviates oxidative stress-related developmental bone injury across complementary models via the Nrf2/GCLC/GCLM antioxidant axis - Gu Xiaoyuan; Mao Jianghao; Mei Aoyu; Ma Li; Ma Juan; Sun Pinghua; Huang Rongping; Li Weixi (PharmaNutrition, 2026)

Phenological shifts in plankton dynamics reshape pressures on anchovy recruitment in the southern coastal waters of the Korean peninsula - Sun-Hee Lee; Juan Carlos Molinero; Eduardo Ramírez-Romero; Joo Myun Park; Marco Scotti; Li-Chun Tseng; Jung-Hoon Kang (Marine Environmental Research, 2026)

An early Late Pleistocene ochre from the Luonan Basin, central China - Jiameng Li; Shuangwen Yi; Xuefeng Sun; Juan Fan; Gaike Zhang; Wenting Xia; Luda Xing; Hongzhu Ma; Huayu Lu; Shejiang Wang (Journal of Human Evolution, 2026)

Microwave-assisted synthesis of FeN Co-doped ZIF-8 derived carbon for low-concentration lithium recovery via CDI: Adsorption performance and mechanism - Yongsi Xie; Jiemei Fu; Chunxue Li; Juan Luo; Rui Ma; Shichang Sun (Desalination, 2026)

Distinct responses of aggregate-associated microbial P-mobilization to coupled changes in nutrient inputs and C:P stoichiometry - Xiaoyan Tang; Juan Ma; Kuilin Wu; Yongyang Luo; Xin Lu; Yanyan Zhang; Youlin Luo; Yingjie Wu; Geng Sun; Igor Bogunovic; Changquan Wang; Hongbo Li; et al. (Applied Soil Ecology, 2026)

Ginsenoside compound K inhibits migration and invasion of melanoma cells by regulating EMT via the IL-6/STAT3 signaling pathway - Xueyan Sun; Qiushi Li; Yuankuan Jiang; Zhe Hou; Qingshan Li; Tingting Xu; Juan Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Catalytic synthesis of salicylic acid via the Kolbe-Schmitt reaction using a polymeric ionic liquid Catalyst - Mengtong Wang; Jiaxin Li; Qiwei Sun; Juan Zhang (Sustainable Chemistry and Pharmacy, 2026)

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Chitosan-assisted cinnamaldehyde utilization and sodium carboxymethyl cellulose-enabled redispersion: A dual strategy for pathogen-specific grape preservation - Yidan Zhang; Lianghuan Huang; Mei Li; Juan Yang; Jisheng Yang; Ningjing Sun; Jialong Wen; Zhiyong Qin (Food Chemistry, 2026)

Whole-genome analysis and probiotic-related phenotypic characterization of the antifungal Lactiplantibacillus plantarum L6 isolated from traditional Chinese paocai - Saihui Sui; Yu Gao; Tianshuai Yuan; Yu Duan; Han Sun; Baokun Li; Juan Dong; Hua Ji; Cailan Wu (Food Bioscience, 2026)

A health-oriented strategy for identifying and controlling high-risk PM2.5 sources: Case study of Heze - Xianmang Xu; Jingsen Zhao; Ying Li; Kun Liu; Chao Zhu; Lei Sun; Tao Li; Wenli Gu; Lidan Xu; Juan Dai; Jin Wang; Wei Cheng; et al. (Environmental Research, 2026)

Fourteen-year manure substitution enhances maize productivity by optimizing soil nutrient availability and microbial community structure - Mengxue Qu; Juan Li; Shanshan Sun; Yinglong Chen; Hao Ren; Hongzhang Wang; Bin Zhao; Baizhao Ren; Jiwang Zhang; Yanqin Ding; Peng Liu (Plant and Soil, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Immunoglobulin M response in different intestinal segments of largemouth bass (Micropterus salmoides) following largemouth bass virus (LMBV) infection - Xinyou Wang; Gaofeng Cheng; Jie Sun; Chang Cai; Zhihao Jiang; Ruiqi Lin; Shun Li; Li Li; Juan Zhao; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Engineering pH and thermostability of β-mannanase from Aspergillus niger for simplified and direct production of manno-oligosaccharides from guar split - Hong Liu; Qi Yao; Dan-yang Sun; Chen-xuan Wu; Qiao-juan Yan; Yan-xiao Li; Zheng-qiang Jiang (Bioresource Technology, 2026)

Cytological and molecular genetic evidence of feminized male gametophyte in the brown alga Saccharina japonica - Xiufeng Zhou; Cailing Yi; Nianchao Xue; Yan Li; Juan Sun; Shuxiu Chen; Yuting Zhai; Liang Shi; Yanling Liu; Nan Zhao; Xia Li; Xiaojie Li; et al. (Algal Research, 2026)

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Sequential bacterial-fungal fermentation upgrades Juncus effusus into an antibacterial biosorbent for cationic dyes - Hai-Juan Zhao; Su Sun; Zhen-Yu Wang; Li Chen; Muhammad Wajid Ullah; Yan-Bo Zhang; Jian-Gang Zhou (Biomass and Bioenergy, 2026)

Genome-wide association analysis identifies novel genetic loci and candidate genes associated with seed dormancy in cultivated peanut - Maoning Zhang; Ziqi Sun; Feiyan Qi; Pei Du; Li Qin; Chenyu Li; Juan Wang; Chenyang Zhi; Jing Xu; Hua Liu; Zhiyuan Zhou; Lijuan Miao; et al. (Theoretical and Applied Genetics, 2026)

Supercritical CO2 Extraction Enhances Bioactivity of Flos Magnoliae Officinalis and Restores Gut Microbiota-Immune Homeostasis in Dysbiosis Mice - Yi Jiang; Juan Bai; Yuxin Zhao; Miqi Hu; Zhaohui Li; Dongdong Sun; Weiyun Wang (Journal of Pharmaceutical Innovation, 2026)

Flavonoids from the whole plants of limonium sinense and their anti-inflammatory activity - Ban-Ban Li; Shao-Wei Sun; Shuang Miao; Li-Juan Yang; Xin-Yu Meng; Kai-Kai Gong; Shi-Zhou Qi; Jin-Jie Zhang (Natural Product Research, 2026)

Terpenoids from Euphorbia ebracteolata (Hayata.) with their multidrug resistance reversal activity - Jia-Le Liu; Jian-Wei Sun; Dong-Xue Wang; Jie Yang; Juan Chen; Jian-Chun Li (Natural Product Research, 2026)

Summer carbon-flow characteristics of a marine ranching ecosystem revealed by Ecopath and stable isotopes: A case study from the Bohai Sea, China - Futang Ma; Jianguang Qin; Yingkun Cao; Juan Pan; Bin Wen; Jiamin Sun; Dapeng Liu; Lixin Gong; Gang Wang; Huixin Liu; Qian Li; Jiale Yan; et al. (Marine Pollution Bulletin, 2026)

Subchronic exposure to decabromodiphenyl ethane impairs cognitive function and induces neuronal ferroptosis via disruption of mitochondria-associated endoplasmic reticulum membranes - Yuanteng Sun; Fei Xiong; Lingjie Wu; Zhihui Liu; Pingping Liu; Wenhao Li; Juan Zhang; Rongli Sun (Journal of Hazardous Materials, 2026)

Recent advances in understanding the modulatory mechanisms of saliva in flavor perception - Kun Zhao; Zikang Xu; Yiyang Li; Qinguo Quan; Yuhan Xie; Juan Wang; Baoguo Sun; Dandan Pu (Food Chemistry, 2026)

3D-printed coaxial intelligent fibers with multimodal sensing capabilities for e-skin - Huilan Jing; Juan Li; Haoran Zheng; Pinjing Lu; Siwen Yu; Jianjun Guo; Yuchuan Cheng; Aihua Sun (Chemical Engineering Journal, 2026)

Study on the pro-inflammatory mechanism mediated by the RANK-SPP1 axis in macrophage immunomodulation during atherosclerosis - Qiyu Sun; Yanbo Hu; Zeming Sun; Mingyan Shang; Zhengyi Li; Juan Shen; Zhenzhen Cui; Jiaxin Yang; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2026)

Terpenylated acetophenones from the root of Ferula ferulaeoides (Steud.) Korov. with selective cytotoxic activity - Yewen Jia; Wen Dang; Xueni Zhang; Yu Sun; Juan Zhang; Degang Qing; Congzhao Fan; Huiming Hua; Yingjie Wang; Ning Li (Phytochemistry, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Source-driven vertical partitioning and stratified risk assessment of trace metals in a subtropical forest soil profile - Juan Li; Tiantian Li; Wenrui Zhao; Xin Sun; Xun Liu; Shuai Liu; Chuansheng Wu (Environmental Pollution, 2026)

Phosphatidylcholine promotes sperm motility by regulating sperm membrane phospholipid homeostasis - Jiwei Li; Yuzhu Cao; Juan Zhang; Yadong Tian; Guirong Sun; Yaling Gu; Xiangtao Kang; Donghua Li (Animal Reproduction Science, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Analysis of volatile components of Yanbian-style sauced beef and the effects of single auxiliary material on its characteristic volatile flavor - Depeng Sun; Yu Jiang; Hongliang Duan; Bowen Qin; Baide Mu; Tingyu Li; Hongmei Li; Juan Wang; Chunxiang Piao; Guanhao Li (International Journal of Gastronomy and Food Science, 2026)

Microwave-assisted extraction enhances the epicatechin and bovine serum albumin the interaction by inducing protein conformational changes - Wen-Ting Duan; Jiang-Feng Yuan; Li-Juan Wang; Meng-Xue Sun; Xiao-Wen Yang; Zhi-Jun Qiu (Food Chemistry, 2026)

A sustainable gelatin-based film reinforced with nanolignin-stabilized pickering emulsion and cellulose nanocrystals from coffee leaves for food preservation - Fangfei Sun; Wenhui Zhao; Juan Zhao; Kun Wang; Lincai Peng; Hui Li (Food Hydrocolloids, 2026)

Provincial policy simulation for steel decarbonization in China: a modular CGE-3E3S coupling framework - Yibo Li; Juan Li; Simin Guo; Mei Sun (Environmental Modelling & Software, 2026)

Aquaporin-1 stabilizes β-catenin to promote NLRP3 inflammasome-mediated pyroptosis in rheumatoid arthritis - Meng-yuan Zhou; Zi-yao Gao; Jing Sun; Wen-cai Long; Juan Zhou; Wen-jing Fang; Xue-chun Wang; Sheng-dong Wu; Rong Li (Apoptosis, 2026)

Evaluating the quality of low-carbon development based on the DPSIR model: evidence from 248 Chinese cities - Cuixia Gao; Dan Wu; Juan Li; Mei Sun (Environment, Development and Sustainability, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Securing CO2 storage in fractured reservoirs: Intelligent characterization of critical natural fracture pathways - Fengyuan Zhang; Jizhou Tang; Jun Zhou; Yubo Liu; Junlun Li; Yifeng Zeng; Zhenguang Zhao; Juan Zhang; Zhe Sun; Wenbo Hu (Fuel, 2026)

Reduction mediated iodide antioxidation: “Chemical Preservation” of precursor solution facilitates construction of high efficiency and stable wide bandgap inverted perovskite solar cells - Chao Liu; Yingchen Li; Hongkun Cai; Boyan Li; Shuping Lin; Qi Sun; Dalong Zhong; Jifeng Liu; Qinwen Guo; Zhiwen Xu; Juan Li; Jian Ni; et al. (Chemical Engineering Journal, 2026)

Anode interface layers constructed in situ by multifunctional carbon dots for ultra-stable aqueous zinc-ion batteries - Qian-Li Ma; Xi-Rong Zhang; Bao-Juan Wang; Hao-Wen Sun; Huan-Ming Xiong (Chemical Engineering Journal, 2026)

Plant growth-promoting functions of endophytic Fusarium annulatum alleviate the damage caused by saline stress in rice - Haoyu Cai; Tongtong Liu; Jiafeng Yu; Wenchao Sun; Lingyun Chang; Shengyi Liu; Ziguang Liu; Junze An; Weilin Cui; Yumei Li; Juan Wu (Planta, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Conventional versus emerging techniques in probiotic enumeration: a comprehensive review - Xiaoyun Sun; Juan Zhang; Jiaci Chen; Longrui Yang; Xiangyi Pang; Yuhang Fan; Xi Chen; Kai Chen; Chuan Liu; Xiaoyu Li; Ailiang Chen (Critical Reviews in Food Science and Nutrition, 2026)

Estuarine plumes: Modulators of dissolved organic matter molecular signatures and biogeochemical fate in coastal ecosystems - Guodong Sun; Na Wang; Wenbo Wang; Yihui Guo; Juan Xu; Zijia Zeng; Penghui Du; Penghui Li; Chen He; Quan Shi; Dongxiao Wang; Wei Xie (Marine Pollution Bulletin, 2026)

A mortise–tenon joint system facilitates precise targeted DNA insertion and replacement in rice - Wenjing Sun; Yaoyao Zhu; Xiuhua Zhang; Xiangbing Meng; Kai Xia; Xin Zhang; Xue Han; Wenbo Pan; Juan Guo; Jiayang Li; Huawei Zhang (Molecular Plant, 2026)

An improved composite eutrophication index for coastal assessment: Laizhou Bay, China - Xuan Liu; Juan Zhang; Yuting Zhao; Lianjie Qiao; Min Li; Yanqun Yang; Shan Sun; Keqiang Li; Xiulin Wang (Marine Environmental Research, 2026)

Biomimetic nanodelivery system for precise elimination of tumor-infiltrating Escherichia coli and enhanced treatment of colorectal cancer - Huiying Liao; Shuang Liu; Xing Sun; Zezhong Huang; Yun Sun; Juan Guo; Fengying Li; Bolong Xu (Chemical Engineering Journal, 2026)

Brain Organoids in Neurodegenerative Disease Modeling: Advances, Applications and Future Perspectives - Wei Wang; Shiyi Tan; Xulei Zuo; Xingxing Gao; Li Ma; Rongli Sun; Geyu Liang; Lihong Yin; Yuepu Pu; Juan Zhang (Molecular Neurobiology, 2026)

Meckel's cartilage midsegment: spatiotemporal dynamics and osteogenic role in mice - Qi Sun; Cheng Li; Lizhu Yin; Chuxuan Xiao; Yi Peng; Juan Liu; Jun Zhang (Cell and Tissue Research, 2026)

Data-driven localization of the TOMGRO model: Cultivar-specific parameter optimization for Shanghai greenhouse tomato production - Yue Sun; Qingqing Ju; Yiyang Li; Linyi Li; Yuhang Wang; Juan Yang; Tingting Qian (Computers and Electronics in Agriculture, 2025)

Assessing the effect of human activity on sediment load in the Second Songhua River Basin, Northeast China, based on the SWAT model - Guilin Lai; Jinxing Sun; Juan Xiao; Zexiang Li; Juan Du; Xiangxiang Wen; Xiangming Xu; Lihong Meng; Xiujuan Li; Keyuan Zhong (Regional Studies in Marine Science, 2025)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Sustainable landfill barrier system: chitosan-modified bentonite with microbial self-healing for groundwater protection in arid regions - Juan Sun; Xinru Zhao; Sisi Ji; Ligang Wang; Qiuying Chen; Yong Zhai; Lulu Li; Fang Liu (Journal of Cleaner Production, 2025)

Spatiotemporal evolution of extreme temperature occurrence time in the Northern Hemisphere under global warming - Zexiang Li; Jinxing Sun; Yan Wu; Juan Xiao; Xiangming Xu; Lihong Meng; Xiujuan Li; Zhiwei Wan; Keyuan Zhong (Global and Planetary Change, 2025)

Thermal-stabilized nanoflower luciferase-based detection of SCC and TPC in raw milk - Longrui Yang; Yuhang Fan; Xiaoyu Li; Xiaoyun Sun; Jiaci Chen; Juan Zhang; Xiangyi Pang; Fengchun Huang; Ailiang Chen (Food Chemistry, 2025)

A nanozyme-based dual-mode sensor for photoelectrochemical and colorimetric assay of Listeria monocytogenes - Mengjie Li; Tingting Han; Chunyue Xia; Juan Xu; Chong Sun; Jiahui Chen; Weimin Xu; Daoying Wang (Food Chemistry, 2025)

Facile and Rapid Synthesis of Cerium-Modified UiO-66-NH2 for Efficient Removal of Safranine T from Aqueous Solutions - Zhengjie Li; Chunxia Fang; Xilong Ma; Yixian Liu; Juan Xie; Pengfei Li; Zhikun Zhang; Xudong Zhao; Hua Sun; Jilong Han (Water Conservation Science and Engineering, 2025)

Analysis of low carbon transformation strategy and CO 2 emission metabolism in the steel industry - Yibo Li; Juan Li; Mei Sun; Simin Guo (Journal of Industrial Ecology, 2025)
As an energy‐intensive sector, the low‐carbon transformation of the steel sector plays a crucial role in achieving China's carbon neutrality goals. Therefore, exploring how learning strategies and incentive mechanisms can synergistically promote the transformation of production and energy structure in the steel sector toward net‐zero emissions is an urgent practical problem that needs to be solved. This study constructed an integrated evaluation framework that combines an improved dynamic computable general equilibrium model with input–output analysis and ecological network analysis, and incorporates learning strategies, carbon taxes, subsidies, carbon trading and other incentive mechanisms into the model to deeply analyze the transformation path of the steel sector in different scenarios. The research not only focuses on the low‐carbon transformation of the steel sector but also comprehensively analyzes the evolution of CO 2 emission metabolism and reveals the complex internal interactions under the background of emission dynamics through a multidimensional network perspective. The results indicate that the steel sector's production and energy structures have significantly changed by implementing incentive mechanisms and introducing learning strategies. In the scenario where carbon taxes, subsidies, and learning strategies work together, it is expected that by 2060, the share of short‐process steelmaking will reach 52.2%, while the proportion of carbon capture and storage equipped in long‐process will exceed 10%. At this time, the short‐process sector's control over other sectors and dependence on the system will increase.

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

ESM-YOLOv11: A lightweight deep learning framework for real-time peanut leaf spot disease detection and precision severity quantification in field conditions - Yapeng Zhang; Juan Liu; Shangzhou Li; Sifan Feng; Ziqi Sun; Yanan Cui; Haijiao Liu; Juanjuan Zhang; Fernando Auat Cheein; Wei Guo (Computers and Electronics in Agriculture, 2025)

Self-sustained Bio-Fenton system driven by Shewanella oneidensis for efficient degradation of persistent organic pollutants under oxygen-limited conditions - Yang-Yang Fan; Xuan Yao; Zhi-Yong Li; Xin-Yu Yang; Ming-Juan Zou; Zi-Yi Zhang; Kun Wu; Ting Huang; Ya-Ning Sun; Xiang Xiao (Journal of Hazardous Materials, 2025)

UPRS-1: A regolith simulant of Utopia Planitia, Mars - Yiming Diao; Honglei Lin; Juan Li; Shouding Li; Changyi Xu; Zhaobin Zhang; Zongyu Yue; Bo Zheng; Xiukuo Sun; Tao Xu; Xinshuo Chen; Yanfang Wu; et al. (Icarus, 2025)

Mixed microbial fermentation with Lactiplantibacillus plantarum and Saccharomyces cerevisiae increases the nutritional bioactive components and flavor substances of pigmented quinoa - Li Zhao; Juan Liao; Tingrui Sun; Shiqi Zhang; Tengfei Wang (Food Chemistry, 2025)

Smartphone-integrated multi-emission Eu-MOF hydrogel for visual, discrimination of antibiotics in milk and honey - Wenxi Zhang; Xinyuan Zhang; Jing Sun; Yanjie Lv; Xiao Li; Juan Hou; Zhongmin Su (Food Chemistry, 2025)

Effects of seminal plasma cholesterol and androgen levels on breeding rooster sperm motility in vitro - Jiwei Li; Lijuan Yang; Juan Zhang; Yadong Tian; Donghua Li; Yaling Gu; Guirong Sun; Xiangtao Kang (Animal Reproduction Science, 2025)

Applicability of Reanalysis Data in Analyzing the Occurrence time of Extreme Temperature Events in China - Zexiang Li; Yan Wu; Jinxing Sun; Juan Xiao; Hua Li; Huaxia Yao; Shuishi Xie; Lihong Meng; Xiujuan Li; Keyuan Zhong (Asia-Pacific Journal of Atmospheric Sciences, 2025)

Evolution of global O3-NOx-VOCs sensitivity before and after the COVID-19 from the ratio of formaldehyde to NO2 from satellite observations - Dakang Wang; Dongchuan Pu; Isabelle De Smedt; Lei Zhu; Xiankun Yang; Wenfu Sun; Hui Xia; Zhaolong Song; Xicheng Li; Juan Li; Aoxing Zhang; Xu Feng; et al. (Journal of Environmental Sciences, 2025)

All-in-one wearable electronic based on bacterial cellulose composite: Integrating strain sensing and energy harvesting - Ping Sun; Zongxue Gu; Duo Xu; Bin Yu; Hui Sun; Juan Li; Nan Zhou; Jing Li; Keshuai Liu; Yingcun Liu; Chong Gao; Weilin Xu (Chemical Engineering Journal, 2025)

Advances in Tetrabromobisphenol A (TBBPA) degradation: A comprehensive review of physicochemical and biotechnological strategies - Wei-Lei Jin; Gui-Xuan Dong; Yang Liu; Yu-Chen Sun; Jia-Cheng Li; Yan Li; Juan Xu (Chemical Engineering Journal, 2025)

Undescribed isoprenoids obtained from Dictamnus dasycarpus Turcz and their cytotoxic activities - Sun Ye; Si-Yi Wang; Yang Xu; Jia-Tong Wu; Juan Pan; Zhi-Chao Hao; Wei Guan; Zhen-Peng Xu; Yuan-Yuan Zhou; Shao-Wa Lv; Qing-Shan Chen; Li-Li Zhang; et al. (Natural Product Research, 2025)

Identification and Functional Analysis of Trehalose Synthesis Genes in Foxtail Millet: Insights into Low-Temperature Stress Response - Yueyue Wang; Yajun Li; Yidan Luo; Yuhua Xu; Bo Zhao; Rong Sun; Juan Zhao; Xukai Li; Yijuan Zhang; Yuanhuai Han; Hongying Li; Hui Zhang (Journal of Plant Growth Regulation, 2025)

The profiling of phytohormone levels with developmental progression in dormant floral buds in peach varieties of differing chilling requirements - Juan Yan; Jiyao Li; Meng Sun; Zhixiang Cai; Binbin Zhang; Jianlan Xu; Ruijuan Ma; Mingliang Yu; Zhijun Shen (Horticulture, Environment, and Biotechnology, 2025)

Three new aliphatic compounds from the roots of Saposhnikovia divaricata and their antiproliferative activity on HepG2 cells - Yan Liu; Jin-Hong Xue; Yan Sun; Fan-Ying Deng; Si-Yi Wang; Juan Pan; Zhi-Chao Hao; Ke-Zhen Chen; Anam Naseem; Qing-Shan Chen; Li-Li Zhang; Hai-Xue Kuang; et al. (Natural Product Research, 2025)

Freeze-induced degradation of organic micropollutants by chlorine - Yuqi Sun; Yingshi Tan; Shengnan Li; Tao Yang; Zhimin Ao; Jin Jiang; Juan Li (Journal of Hazardous Materials, 2025)

Nanocatalytic-phytoremediation synergistic strategy: Functional carbon nanodots enhancing nonylphenol biodegradation in contaminated soil - Qiong Chen; Junjie Huang; Junbo Zhou; Lanxuan Sun; Jianing Yang; Qiuyu Shu; Yiwen Sun; Juan Li; Mei Yan (Journal of Hazardous Materials, 2025)

Toxicity of 6PPD to the stony coral Pocillopora damicornis in different developmental stages - Bing Yang; Qingsong Yang; Junde Dong; Jie Li; Shan Liu; Ying Zhang; Huiming Sun; Chang Chen; Juan Ling (Journal of Hazardous Materials, 2025)

An ion-selective Li1.3Al0.3Ti1.7(PO4)3 membrane for electrolytic lithium extraction from brine - Tong Zhou; Nan Zhang; Qi Li; Guoyao Li; Haidong Sun; Chenglan Zhang; Juan Li; Hezhou Liu; Huanan Duan (Desalination, 2025)

Effects of Continuous Grafting on the Growth and Selenium Accumulation Characteristics in the Post-Generations of Tomato - Shiling Meng; Xiaoli Song; Wende Zhou; Juan Huang; Yatian Zhao; Wanjia Tang; Yi Tang; Bo Sun; Huanxiu Li; Zhi Huang (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Comprehensive assessment of chemical and microbial inducers for coral larval settlement across diverse coral species - Huiming Sun; Qingsong Yang; Junde Dong; Jie Li; Chang Chen; Xiaoyu Tang; Ying Zhang; Juan Ling (Frontiers in Marine Science, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Development of a stable luciferase@nanoflower-based method for the sensitive detection of pesticide residues in milk - Xiaoyu Li; Fengchun Huang; Juan Zhang; Jiaci Chen; Xiangyi Pang; Longrui Yang; Xiaoyun Sun; Yuhang Fan; Ailiang Chen; Qingli Yang (Food Chemistry, 2025)

Preparation of aldehyde-recognition nanofiber label for monitoring oxidative deterioration in processed meat products - Mengjie Li; Chong Sun; Shenjun Chen; Huiwen Liu; Juan Xu; Yongzhi Zhu; Daoying Wang (Food Chemistry, 2025)

A comprehensive geological engineering site selection for lunar research station and base on a global scale - Xinshuo Chen; Shouding Li; Juan Li; Zongyu Yue; Zhaobin Zhang; Tao Xu; Bo Zheng; Xiukuo Sun; Yiming Diao; Jianming He; Xiao Li; Jianbing Peng (Engineering Geology, 2025)

Chemical constituents from Dictamnus dasycarpus Turcz. and their chemotaxonomy value - Yan Liu; Guangzhi Li; Ye Sun; Jiatong Wu; Shiqi Xu; Juan Pan; Junnan Li; Luxin Li; Zhichao Hao; Wei Guan; Yuanyuan Zhou; Qi Shi; et al. (Biochemical Systematics and Ecology, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Molecular mechanisms of UCP1-independent thermogenesis: the role of futile cycles in energy dissipation - Quanhao Sun; Xinyue Cui; Dong Yin; Juan Li; Jiarui Li; Likun Du (Journal of Physiology and Biochemistry, 2025)

Carbon emissions and regional differences of Chinese urban buildings under multi-dimensional key influencing factor identification - Juan Li; Mei Sun; Lixin Tian (Environment, Development and Sustainability, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Recent innovations in Grifola frondosa polysaccharides: production, properties, and their biological activity - Umar Zeb; Tariq Aziz; Wen-Jing Sun; Abdul Haleem; Guo-Qiang Guan; Li-Juan Meng; Lei Sun; Feng-Jie Cui (Food Bioscience, 2025)

Sustainable fabrication of fluorescent spiropyran-functionalized chitin nanofibers via amino-yne click chemistry for UV-blocking and smart environmental monitoring - Juan Yu; Bowen Li; Yingyin Liu; Hanlu Ji; Liang Liu; Hong Sun; Yimin Fan (Chemical Engineering Journal, 2025)

Integration of BSA-seq and high-resolution mapping reveals genomic regions and candidate genes controlling seed oil accumulation in peanut (Arachis hypogaea L.) - Ziqiang Mo; Feiyan Qi; Ziqi Sun; Li Qin; Juan Wang; Mengmeng Wang; Stefano Pavan; Guoquan Chen; Xiao Wang; Hongfei Liu; Yaojun Hu; Yuzhen Zheng; et al. (Theoretical and Applied Genetics, 2025)

Genomic insights into the genetic basis of the seed size and weight revealed by the Chinese peanut key landraces - Juan Wang; Bingke Jiao; Chunjuan Qu; Caixia Yan; Dachuan Shi; Chen Jiang; Mei Yuan; Wenjiao Wang; Cuiling Yuan; Xiaobo Zhao; Quanxi Sun; Yifei Mou; et al. (Theoretical and Applied Genetics, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Antibiotics and endocrine disrupting chemicals in effluent from wastewater treatment plants of a mega-city affected the water quality of juvenile Chinese sturgeon habitat: Upgrades to wastewater treatment processes are needed - Qian Wang; Hanwen Xu; Shanfei Gan; Ruihua Sun; Yueping Zheng; Nicholas J. Craig; Wei Sheng; Juan-Ying Li (Marine Pollution Bulletin, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

Spatiotemporal evolution of temperature extremes onset times and their association with atmospheric circulations in the Poyang Lake basin, China - Mei Wang; Yan Wu; Juan Du; Yawen Yang; Jinxing Sun; Zexiang Li; Juan Xiao; Lihong Meng; Xiangming Xu; Keyuan Zhong (International Journal of Biometeorology, 2025)

Comprehensive assessment of chemical and microbial inducers for coral larval settlement across diverse coral species - Huiming Sun; Qingsong Yang; Junde Dong; Jie Li; Chang Chen; Xiaoyu Tang; Ying Zhang; Juan Ling (Frontiers in Marine Science, 2025)
Introduction Coral restoration efforts increasingly focus on enhancing larval settlement and post-settlement survival. However, the species-specific efficacy of different settlement inducers remains inadequately understood, limiting optimization of restoration protocols. Methods This study systematically assessed the effectiveness of three settlement inducers—Crustose coralline algae (CCA), Chemical (CaCl 2 ), and Microbial ( Metabacillus sp. cB07)—across seven coral species, including both brooders and broadcast spawners. Larvae were exposed to gradient concentrations of each inducer to determine optimal concentrations and treatment durations. Effects on larval survivorship, metamorphosis, and settlement were measured. Post-settlement recruits treated with optimized procedures were further evaluated for metabolic rates, morphology, survival, and growth. Results Optimal inducer concentrations and treatment durations varied significantly among coral species, with CaCl 2 (10–60 mmol/L) and cB07 (3 × 10 6 –3 × 10 7 cfu/mL) showing broad-spectrum activity comparable to CCA. CCA induced the highest settlement rates (43.3%–93.3%) within 1–2 days, CaCl 2 showed moderate induction (23.3%–60.3%) within 0.5–4 days, and cB07 exhibited similar efficacy (26.7%–60.0%) within 2–4 days. Biological effects differed: CaCl 2 accelerated metamorphosis but lowered survival in sensitive species, while cB07 delayed metamorphosis and suppressed respiratory rates, indicating higher toxicity. Post-settlement, recruits induced by CCA and CaCl 2 had higher survival and calcification rates than those induced by cB07. Discussion These findings underscore the necessity of tailoring settlement inducer protocols to the species-specific life histories and physiological responses of corals. Integrating metabolic and ecological insights offers practical guidelines to enhance coral restoration success amid growing environmental pressures.

Mechanisms of soil persistent organic carbon loss in alpine ecosystems: Insights into microbial and calcium spatial footprint - Jie Shen; Bangfei Ou; Yanbao Lei; Yuting He; Juan Xue; Xianzhi Deng; Changquan Wang; Yiding Li; Geng Sun (Soil Biology and Biochemistry, 2025)

Chromones from Saposhnikovia divaricata and their inhibition of IL-1β-induced proliferative activity in SW982 cells - Yan Liu; Junnan Li; Yan Sun; Juan Pan; Yumeng Luo; Wei Guan; Qingshan Chen; Lili Zhang; Anam Naseem; Haixue Kuang; Bingyou Yang (Phytochemistry, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Cobalt-catalyzed reversible deposition/dissolution of MnO2 for enhancing the long-cycle stability of aqueous Zn-Mn batteries - Changpeng Xian; Ruilin He; Qianwei Chen; Qiulin Li; Yandong Ma; Shu-juan Bao; Wei Sun; Hao Chen; Maowen Xu (Chemical Engineering Journal, 2025)

Mapping rice lodging severity using dual-pol Sentinel-1 SAR data: polarimetric parameters, lodging sensitivity, and fuzzy classification modelling - Mo Wang; Qing Sun; Xianghong Che; Li Chen; Yunpeng Cui; Juan Liu; Jinming Wu; Ting Wang; Huan Li (International Journal of Remote Sensing, 2025)

Effects of different carbohydrates on growth, hepatic glucose metabolism, and gut microbiome of Florida pompano (Trachinotus carolinus) - Juan F. Paredes; Michael Habte-Tsion; Marty Riche; Sahar Mejri; David Bradshaw; Li Sun Chin; Carlie Perricone; Paul S. Wills (Aquaculture, 2025)

Inorganic substrates in frozen solutions: Transformation mechanisms and interactions with organic compounds - A review - Yuqi Sun; Juan Li; Shengnan Li; Juntian Li; Binghua Jing; Tao Yang; Yi Yang; Zhimin Ao (Water Research, 2025)

Genomic characteristics and antimicrobial resistance of the underreported zoonotic pathogen Streptococcus pasteurianus and its co-colonization with Streptococcus suis - Shuoyue Wang; Xinchun Li; Chenxu Zheng; Juan J. Quereda; Jie Sun; Huochun Yao; Zongfu Wu (Veterinary Microbiology, 2025)

A comparative study of steam gasification and combustion methods for landfill stale waste (LSW) treatment - Muhammad Irfan Rajput; Jian Li; Beibei Yan; Guanyi Chen; Ruqayia Khan; Yunan Sun; Juan Zhao (Journal of Environmental Management, 2025)

Metabolic profiling and amino acid evolution in fermented oats: Insights from UPLC-MS/MS and PLS-DA analysis - Juan Sun; Xue LaMei; Waleed AL-Ansi; Mingcong Fan; Yan Li; Haifeng Qian; Liuping Fan; Li Wang (Food Bioscience, 2025)

Advancing predictive, preventive, and personalized medicine in eyelid diseases: a concerns-based and expandable screening system through structural dissection - Jing Cao; Kun You; Peifang Xu; Yiming Sun; Ji Shao; Yifan Zhou; Huimin Li; Lixia Lou; Qi Miao; Juan Ye (EPMA Journal, 2025)
Background/aims Early recognition of eyelid morphological abnormalities was crucial, as untreated conditions could lead to blinding complications. An eyelid screening system that could provide both anatomical and pathological information was essential for formulating personalized treatment strategies. This study aimed to develop a clinically concerns-based framework capable of identifying common eyelid diseases requiring further intervention by evaluating individual anatomical and pathological changes. This approach would enhance individualized and efficient prevention, while supporting targeted treatment strategies. Methods The eyelid disorder screening system, Eyetome, was developed based on a morphological atlas and comprised four modules designed to identify 14 common eyelid disorders and pathological changes. A total of 6180 eye patches were analyzed to extract anatomical and pathological features. The performance of Eyetome was evaluated using average accuracy (aACC) and F1 score, with comparisons made against traditional models and ophthalmologists. To assess the system’s expandability, an additional test was conducted in a multimorbidity scenario. Results Eyetome demonstrated high performance in recognizing single diseases, achieving an aACC of 98.83% and an F1 score of 0.93. The system outperformed classic models, with an aACC of 98.83% compared to 96.72% for Desnet101 and 97.59% for Vit. Additionally, Eyetome’s aACC exceeded that of a junior ophthalmologist (JO) (97.11%) and was comparable to a senior ophthalmologist (SO) (98.69%). In the extended multimorbidity dataset, Eyetome maintained robust performance with an accuracy of 97.97%, surpassing JO (95.47%) and closely matching SO (97.81%). Conclusions This study developed a clinical concerns-based system for screening and monitoring eyelid disorders, aimed at supporting predictive diagnosis, preventing diseases progression, and facilitating more effective, patient-centered treatment of common eyelid disorders, aligning with the principles of predictive, preventive, and personalized medicine (PPPM/3PM). The system’s interpretability, scalability, and user-friendly data acquisition design could further enhance its acceptance among both doctors and patients, facilitating the shift from reactive medicine to proactive precision medicine.

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

Plasticization of gelatin/chitosan films with deep eutectic solvents and addition of Flos Sophora Immaturus extracts for high antioxidant and antimicrobial - Quanling Zhao; Xi Huang; Lijun Qian; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Corrosion behavior of WC-NiMoCrFeCo coating in seawater environment: Positive corrosion inhibition of a novel dynamic reaction product - Yu-Hang Zhang; Yao-Ning Sun; Xiu-Juan Fan; Bo-Kai Liao; Chun-Ming Deng; Shuang-Jian Li; Chao Wang; Yi-Fei Xv; Kang Li; Yi-Zhe Lv (Chemical Engineering Journal, 2025)

FEC-driven surface conversion reaction to construct lithiophilic and air-stabilized LLZTO for durable lithium battery - Qiulin Li; Zhi Xiao; Kang Pu; Yandong Ma; Changpeng Xian; Wei Sun; Maowen Xu; Shu-Juan Bao (Chemical Engineering Journal, 2025)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Cdh23 Gene Mutation–Induced Vestibular Dysfunction in Mice: Abnormal Stereocilia Bundle and Otolith Development and Activation of p53/FoxO Signaling Pathway - Lihuan Tang; Yuancheng Wu; Kai Zhang; Daoli Xie; Xiaojing Kuang; Lan Wang; Zehua Sun; Ruishuang Geng; Juan Hu; Yan Sun; Tihua Zheng; Bo Li; et al. (Journal of Molecular Neuroscience, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Pacific Walker Circulation modulated millennial-scale East Asian summer monsoon rainfall variability over the past 40 kyr - Yi Zhong; Yuxing Liu; Xiaojing Du; Xiaoxu Shi; Xing Xu; Zhengyao Lu; Stefanie Kaboth-Bahr; Mark J. Dekkers; Juan C. Larrasoaña; Keiji Horikawa; Chijun Sun; Liang Ning; et al. (Global and Planetary Change, 2025)

Gelatin-based composite film integrated with nanocellulose and extract-metal complex derived from coffee leaf for sustainable and active food packaging - Fangfei Sun; Juan Zhao; Peng Shan; Kun Wang; Hui Li; Lincai Peng (Food Hydrocolloids, 2025)

Self-signaling colorimetric sensor for selective detection of dopamine based on CoFe2O4 nanozyme accelerated dopamine polymerization - Panpan Sun; Juan Chen; Qian Li; Mingyue Luo; Wenzhuo Chang; Zhonghua Xue (Analytica Chimica Acta, 2025)

Studying the cement industry's policy incentives and the optimization path for carbon neutrality technology based on an integrated model - Juan Li; Yibo Li; Mei Sun; Yanzi Guo; Faxin Cheng; Cuixia Gao (Environment, Development and Sustainability, 2025)

Insights to the roles of nitrogen-doped biochar in anaerobic digestion - Zhang-Wei He; Sheng-Jie Sun; Ai-Hua Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhi-Hua Li; Ai-Jie Wang; Wen-Zong Liu (Process Safety and Environmental Protection, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

A telomere-to-telomere genome assembly of the cultivated peanut - Xiaobo Wang; Ziqi Sun; Feiyan Qi; Zhiyuan Zhou; Pei Du; Lei Shi; Wenzhao Dong; Bingyan Huang; Suoyi Han; Stefano Pavan; Meng Zhang; Mengjie Cui; et al. (Molecular Plant, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Rapid analysis of salivary glucose content using MOF/MIPs biomimetic microfluidic paper chips - Ningning Li; Ying Zhou; Hao Sun; Nan Wang; Nan Yang; Peiyao Ren; Lanjun Fu; Yiming Zhang; Wei Liu; Yanjie Li; Juan Jin (Chemical Engineering Journal, 2025)

Research progress of chlorine corrosion resistance in seawater electrolysis: Materials and technologies - Li-Juan Yang; Hao-Yue Guan; Shuo Yuan; Tao Sun; An-Ning Jiang; Ji-Jun Feng (Chemical Engineering Journal, 2025)

Dynamic changes of extreme temperature occurrence time in China - Zexiang Li; Jinxing Sun; Juan Xiao; Xiangxiang Wen; Guilin Lai; Mei Wang; Juan Du; Xiujuan Li; Xiangming Xu; Keyuan Zhong (Theoretical and Applied Climatology, 2025)

A novel ATP2A2 mutation in Darier and genotype phenotype: correlation analysis - Xiaofen Guo; Juan Du; Mingwei Lv; Yi Hu; Qi Zhen; Weiwei Chen; Yirui Wang; Zhuo Li; Chunmeng Liu; Xinyu Feng; Wanli Niu; Yu Zhang; et al. (Genes & Genomics, 2025)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

Upgrading pyrolysis carbon black by recyclable ferrate/alkaline treatment with the assistance of ultrasound - Ke Liu; Zhengqing Kong; Yanchun Han; Liying Zhang; Juan Liu; Heyue Sun; Fangshuo Li; Shouke Yan; C.D. Midhun Dominic; Hao Wu; Lu Zong; Jianming Zhang; et al. (Journal of Cleaner Production, 2024)

Purification, structural identification, in vitro hypoglycemic activity and digestion characteristics of polysaccharides from the flesh and peel of wampee (Clausena lansium) - Jun-ye He; Juan-li Fang; Chong-yang Yu; Xu Zhang; Peng-peng Sun; Yuan-yuan Ren (Food Research International, 2024)

Toothpick DNA extraction combined with handheld LAMP microfluidic platform for simple and rapid meat authentication - Bin Xiao; Tianping Zhou; Nan Wang; Juan Zhang; Xiaoyun Sun; Jiaci Chen; Fengchun Huang; Junbo Wang; Nan Li; Ailiang Chen (Food Chemistry, 2024)

Effect of combined treatments of hydrolysis and succinylation on the solubility and emulsion stability of rennet casein and micellar casein - Hongjuan Li; Chuan Ren; Dongyu Hou; Xiaobao Qiu; Juan Zhang; Xiaohong Chen; Yang Zou; Guilian Sun; Kewen Li; Hongbo Li; Jinghua Yu (Food and Bioproducts Processing, 2024)

Li3VO4 mesocubes with exposed (200) facet as dendrite-free anode materials for high-safety Li-ion batteries - Didi Wang; Yijing Zhao; Pengchao Liu; Chunsheng Li; Chen Yang; Yan Sun; Meiqi Zhang; Yuqing Yang; Qing Wang; Guoliang Dai; Yuhai Dou; Chao Wu; et al. (Chemical Engineering Journal, 2024)

Effects of Mutual Grafting on Fruit Quality in Post-grafting generation of Two Genotypes Cherry Tomato (Lycopersicon esculentum) - Zhi Huang; Shiling Meng; Huizhong Luo; Wende Zhou; Juan Huang; Yatian Zhao; Xiaoli Song; Yi Tang; Bo Sun; Huanxiu Li (Journal of Soil Science and Plant Nutrition, 2024)

Independent induction of calluses and nematophytes from exfronds and their potential application for kelp cultivation and germplasm conservation - Pingping Tian; Weiwei Wang; Yan Li; Guangjin Liang; Juan Sun; Yanling Liu; Guanpin Yang; Xiaojie Li (Journal of Applied Phycology, 2024)

Simultaneous determination of somatic cell count and total plate count in raw milk based on ATP bioluminescence assay - Longrui Yang; Xiaoyun Sun; Jiaci Chen; Juan Zhang; Xiaoyu Li; Song Qu; Kai Wu; Fengchun Huang; Ailiang Chen (Analytica Chimica Acta, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Development of halochromic labels based on binary systems of cationic guar gum and κ-carrageenan loaded with alizarin red S for monitoring milk and seafood freshness - Jiaci Chen; Juan Zhang; Chuan Liu; Yumeng Sun; Xiaoxu Han; Xiaoyun Sun; Xiaoyan Pei; Fengchun Huang; Xiangyang Li; Ailiang Chen (Food Hydrocolloids, 2024)

LncRNA TUG1 regulates mir-34a-5p / SIRT6 to participate in benzene-induced hematotoxicity through PI3K / AKT /mTOR signaling pathway - Rongli Sun; Jinyan Liu; Xiaoqin Li; Kai Xu; Jiawei Huang; Daqin Wang; Fei Xiong; Juan Zhang; Yuepu Pu (Food and Chemical Toxicology, 2024)

Current regulates electron donors for heterotrophic and autotrophic microorganisms to enhance sulfate reduction in three-dimensional electrode biofilm reactors - Yang Liu; De-Zhuang Gao; Jia-Qi Fan; Yu-Chen Sun; Wei-Lei Jin; Jia-Cheng Li; Jie Deng; Juan Xu (Chemical Engineering Journal, 2024)

Effect of calculation unit division in distributed hydrological models on the analysis of hydrological effects of land use change - Jinxing Sun; Juan Xiao; Zexiang Li; Guilin Lai; Juan Du; Shuishi Xie; Xiangming Xu; Lihong Meng; Xiujuan Li; Keyuan Zhong (CATENA, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Apomixis in Saccharina japonica: Parthenogenesis in male and apogamy in female gametophytes - Shutao Yue; Nianchao Xue; Cailing Yi; Juan Sun; Xia Li; Shuxiu Chen; Linan Zhang; Xiaojie Li (Aquaculture, 2024)

The protective effect of glucose selenol on cadmium-induced testicular toxicity in male rat - Xinyi Yang; Jinzhou Huang; Juan Wang; Huimin Sun; JinJin Li; Zhi Wang; Qisheng Song (Reproductive Toxicology, 2024)

Study on the grading preparation of multifunctional materials and application from coal gasification fine slag - Song Qiao; Yulong Ma; Yonggang Sun; Li Zhu; Jing Ma; Jingdan Gao; Yingbo Zhu; Juan Zhang; Lei Wang; Min Xu; Yuhua Wu; Wenxin Ji; et al. (Process Safety and Environmental Protection, 2024)

Environmental water-mediated dual-mechanism regulation of PtCuδ-MnOx-catalyzed acetone oxidation: Enhancement of MvK and inhibition of L-H mechanism - Lei Wang; Xin Zhang; Yonggang Sun; Yulong Ma; Min Xu; Juan Zhang; Yingbo Zhu; Li Zhu; Song Qiao; Jing Ma; Jinpeng Wei; Feng Lin (Journal of Environmental Chemical Engineering, 2024)

Biochar alleviates inhibition effects of humic acid on anaerobic digestion: Insights to performances and mechanisms - Sheng-Jie Sun; Fei Wang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhihua Li; Wenzong Liu (Environmental Research, 2024)

Safety, pharmacokinetics, and food-effect of pivmecillinam after single- and multiple-dose in healthy Chinese subjects: a phase I study - Lu-Lu Zhang; Yi Liu; Qiong-Ye Huang; Hong-Wen Zhang; Li-Jun Xie; Juan Chen; Li Ding; Chen Zhou; Lu-Ning Sun; Yong-Qing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Alleviating Coral Thermal Stress via Inoculation with Quorum Quenching Bacteria - Qingsong Yang; Bing Yang; Bin Yang; Wenqian Zhang; Xiaoyu Tang; Huiming Sun; Yanying Zhang; Jie Li; Juan Ling; Junde Dong (Marine Biotechnology, 2024)

Dynamic Optimal Obstacle Avoidance Control of AUV Formation Based on MLoTFWA Algorithm - Juan Li; Donghao Sun; Di Wu; Huadong Zhang (Journal of Marine Science and Engineering, 2024)
In addressing the optimal formation obstacle avoidance control problem for Autonomous Underwater Vehicles (AUVs) in environments with unknown and moving obstacles, this paper employs the Modified Fireworks Algorithm based on a Loser Elimination Mechanism (MLoTFWA) and constructs a Distributed Model Predictive Control (DMPC) framework to achieve obstacle avoidance for AUV formations. Initially, a prediction model is established, followed by feedback compensation to mitigate the effects of unknown perturbations. An appropriate fitness function is then formulated, and enhancements such as the loser elimination rule are introduced to optimize the fireworks algorithm. Additionally, the concept of an adaptive DMPC prediction window is proposed to conserve resources. The local and global stability of the DMPC formation control framework is theoretically proven. Simulations verify that the control system based on the DMPC framework ensures safe obstacle avoidance for the formation, maintains formation consistency, and achieves the shortest and smoothest path. The improved fireworks algorithm demonstrates superior performance compared with the original fireworks algorithm and other optimization algorithms. In testing, the improved fireworks algorithm exhibits better adaptability, higher average fitness, and best fitness, along with a significantly faster convergence speed. Compared with the ordinary fireworks algorithm, the convergence speed is reduced by 30%.

π-Conjugated nitroxide radicals for resistive switching devices - Xiaoguang Hu; Juan Ding; Hanjiao Chen; Yan Hou; Huaqing Li; Yajing Sun; Xuying Liu (Science Bulletin, 2024)

Flexible roles of TiO2 in enhancing carrier separation for the high photocatalytic performance of water treatment under different spectrum sunlight - Zhongxi Lu; Shaosheng Rao; Shuo Li; Xiaohui Yu; Haopeng Jiang; Yangyang Sun; Weikang Wang; Lele Wang; Juan Yang; Qinqin Liu (Journal of Water Process Engineering, 2024)

A review of flow field characteristics in submerged hollow fiber membrane bioreactor: Micro-interface, module and reactor - Qingwen Qin; Guang Yang; Juan Li; Min Sun; Hui Jia; Jie Wang (Journal of Environmental Management, 2024)

Maternal brown rice diet alleviates adverse effects of maternal obesity on offspring metabolism via enhancing DNA demethylation of AdipoR2 - Lamei Xue; Yu Wang; Juan Sun; Yujie Sun; Kuiliang Zhang; Mingcong Fan; Haifeng Qian; Li Wang; Yan Li (Food Bioscience, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Sulfadiazine degradation by hydroxyl radical and direct electron transfer pathways in the self-prepared boron doped diamond electrochemical process - Lingwei Meng; Ruibin Zheng; Renzhen Cheng; Juan Li; Honglan Li; Mingchang Gao; Shaofang Sun; Liping Qiu; Qi Qiu (Journal of Water Process Engineering, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Critical review and recent advances of emerging real-time and non-destructive strategies for meat spoilage monitoring - Jiaci Chen; Juan Zhang; Nan Wang; Bin Xiao; Xiaoyun Sun; Jiapeng Li; Ke Zhong; Longrui Yang; Xiangyi Pang; Fengchun Huang; Ailiang Chen (Food Chemistry, 2024)

Indole-3-acetic acid regulating the initial adhesion of microalgae in biofilm formation - Zhihuai Xie; Zixuan Ou; Meili Zhang; Guotao Tang; Xiaoshi Cheng; Wangbei Cao; Jingyang Luo; Fang Fang; Yingqiang Sun; Ming Li; Juan Cai; Qian Feng (Environmental Research, 2024)

Effects of dietary selenized glucose on intestinal microbiota and tryptophan metabolism in rats: Assessing skatole reduction potential - Zhi Zeng; Bo Lv; Yun-e Tang; Huimin Sun; Shunfeng Li; Yuan He; Juan Wang; Zhi Wang (Environmental Research, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

A graphene oxide-assisted protein immobilization paper-tip immunosensor with smartphone and naked eye readout for the detection of okadaic acid - Yifan Shao; Xiaotong Li; Xiaoxiao Qi; Juan Li; Sheng Zhao; Peiyan Sun; Hongliang Wang; Yongqiang Cheng; Ziwei Zhang; Longyu Chen; Xi Zhang; Meijia Zhu (Analytica Chimica Acta, 2024)

Impact of greening trends on biogenic volatile organic compound emissions in China from 1985 to 2022: Contributions of afforestation projects - Yichao Gai; Lei Sun; Siyuan Fu; Chuanyong Zhu; Changtong Zhu; Renqiang Li; Zhenguo Liu; Baolin Wang; Chen Wang; Na Yang; Juan Li; Chongqing Xu; et al. (Science of The Total Environment, 2024)

Various functions of detoxification enzymes against insecticides in Nilaparvata lugens selected by toxicity assays and RNAi methods - Jun Yang; Li-Yuan Sun; Ruiyan Ma; Rui Tang; Juan-Ying Zhao; Qing-Nian Cai (Pesticide Biochemistry and Physiology, 2024)

Effect of plant polysaccharides on the conformation and gel properties of the Eugenol–Myofibrillar protein complex - Jiamei Li; Ning An; Geyi Ren; Lijie Wang; Nengmao Chen; Jingtao Sun; Qingling Wang; Juan Dong (Food Bioscience, 2024)

Preparation and characterization of whey protein isolate-dextran-proanthocyanidins ternary complexes: Formation mechanism, physicochemical stability - Hongjuan Li; Juan Zhang; Yifei Wu; Chuan Ren; Xiaobao Qiu; Hongbo Li; Guilian Sun; Kewen Li; Jinghua Yu (Food Hydrocolloids, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Effects of Rhizosphere Microorganisms Associated with Suaeda Salsa on the Growth and Salt Stress Resistance of Alfalfa - Jinxia Chen; Qian Zhang; Xihu Qie; Yajuan Che; Dantong Lv; Yuxuan Gao; Fuhong Miao; Shuo Li; Feng He; Juan Sun; Chao Yang (Journal of Soil Science and Plant Nutrition, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

hP-MSCs attenuate severe acute pancreatitis in mice via inhibiting NLRP3 inflammasome-mediated acinar cell pyroptosis - Shuang Lyu; Shuirong Liu; Xin Guo; Yaolei Zhang; Zhongyu Liu; Shan Shi; Wenya Li; Juan Pei; Yonghong Fan; Hongyu Sun (Apoptosis, 2024)

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Inhibition of potassium cinnamate to blueberry Alternaria fruit rot - Yuxuan Li; Juan Zhang; Yajuan Wang; Jiaqi Wang; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Journal of Stored Products Research, 2024)

Kidney toxicity and transcriptome analyses of male ICR mice acutely exposed to the mushroom toxin α-amanitin - Zhijun Wu; Haijiao Li; Wenjin Zhao; Min Zheng; Juan Cheng; Zhengjie Cao; Chengye Sun (Food and Chemical Toxicology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

PM2.5-induced premature senescence in HUVECs through the SIRT1/PGC-1α/SIRT3 pathway - Qing Yan; Rao Zheng; Yi Li; Juan Hu; Meidi Gong; Manman Lin; Xuecong Xu; Jing Wu; Shikun Sun (Science of The Total Environment, 2024)

Influence mechanism of anions on iron doping into swine bone char: Promoting non-radical oxidation of acetaminophen in a Fenton-like system - Yifeng Zeng; Hongwei Luo; Dongqin He; Jun Li; Anping Zhang; Jianqiang Sun; Juan Xu; Xiangliang Pan (Science of The Total Environment, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Volatile compound dynamics in oats solid-state fermentation: A comparative study of Saccharomyces cerevisiae A3, Lactococcus lactis 4355, and Lactobacillus plantarum 2329 inoculations - Juan Sun; Waleed AL-Ansi; Mingcong Fan; Yan Li; Haifeng Qian; Liuping Fan; Li Wang (Food Chemistry, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Trace element geochemistry of sediments in the Pearl River Estuary and its implication for provenance - Yi Sun; Baolin Liu; Houyi Zheng; Yu Zou; Juan Yang; Qinyue Li (Regional Studies in Marine Science, 2024)

Application of controlled-release urea increases maize N uptake, environmental benefits and economic returns via optimizing temporal and spatial distributions of soil mineral N - Mingxue SUN; Juan LI; Lili ZHANG; Xiaomeng SU; Ning LIU; Xiaori HAN; Songjiang WU; Zhentao SUN; Xiangdong YANG (Pedosphere, 2024)

Li-decorated B-doped biphenylene network for reversible hydrogen storage - Li-Juan Ma; Yilan Sun; Jianfeng Jia; Hai-Shun Wu (Fuel, 2024)

Revitalizing mitochondrial function and empowering spinal cord recovery using copper-catalyzed Pdots - Bao-Feng Zhao; Fan Wang; Jia-Chen Sun; Jin-Peng Gao; Li-Juan Zhao; Zhao-Liang Shen; Zhi-Peng Li; Yi-Xuan Wang; Yuan Wang; Dan Li; Xi-Fan Mei (Chemical Engineering Journal, 2024)

Using a Laboratory Column Experiment to Explore the Influence of an Antecedent Dry Period on the Nutrient Removal of a Bioretention Filter - Wei Zhang; Zimeng Zhuang; Juan Li; Huichao Sun; Wu Che (Water, Air, & Soil Pollution, 2024)

Aerobic Glycolysis Induced by mTOR/HIF-1α Promotes Early Brain Injury After Subarachnoid Hemorrhage via Activating M1 Microglia - Xin-Gang Sun; Xue-Hong Chu; Ivan Steve Godje Godje; Shao-Yu Liu; Hui-Yu Hu; Yi-Bo Zhang; Li-Juan Zhu; Hai Wang; Chen Sui; Juan Huang; Ying-Jie Shen (Translational Stroke Research, 2024)

Insidious transmission of Mycobacterium tuberculosis in Ordos, China: a molecular epidemiology study - Hailin Sun; Zichun Ma; Fuli Ai; Bing Han; Peng Li; Juan Liu; Yiheng Wu; Yufeng Wang; Bing Li; Dan Qi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

Effect of autologous bone marrow stem cells-scaffold transplantation on the ongoing pregnancy rate in intrauterine adhesion women: a randomized, controlled trial - Hui Zhu; Taishun Li; Peizhen Xu; Lijun Ding; Xianghong Zhu; Bin Wang; Xiaoqiu Tang; Juan Li; Pengfeng Zhu; Huiyan Wang; Chenyan Dai; Haixiang Sun; et al. (Science China Life Sciences, 2024)

Tissue-specific populations from amniotic fluid-derived mesenchymal stem cells manifest variant in vitro and in vivo properties - Nengqing Liu; Yi Cheng; Ding Wang; Hongmei Guan; Diyu Chen; Juan Zeng; Dian Lu; Yuanshuai Li; Yinghong Yang; Qian Luo; Lifen Zhu; Bin Jiang; et al. (Human Cell, 2023)
Amniotic fluid derived mesenchymal stem cells (AFMSCs), shed along the fetal development, exhibit superior multipotency and immunomodulatory properties compared to MSCs derived from other somatic tissues (e.g., bone marrow and fat). However, AFMSCs display heterogeneity due to source ambiguity, making them an underutilized stem cells source for translational clinical trials. Consequently, there is an urgent need to identify a method to purify the AFMSCs for clinical use. We found that the AFMSCs can be categorized into three distinct groups: kidney-specific AFMSCs (AFMSCs-K), lung-specific AFMSCs (AFMSCs-L), and AFMSCs with an undefined tissue source (AFMSCs-X). This classification was based on tissue-specific gene expression pattern of single cell colony. Additionally, we observed that AFMSCs-X, a minority population within the AFMSCs, exhibited the highest multipotency, proliferation, resistance to senescence and immuno-modulation. Our results showed that AFMSCs-X significantly improved survival rates and reduced bacterial colony forming units (CFU) in cecal ligation and puncture (CLP)-induced septic mice. Therefore, our study introduces a novel classification method to enhance the consistency and efficacy of AFMSCs. These subpopulations, originating from different tissue source, may offer a valuable and innovative resource of cells for regenerative medicine purposes.

Porcine β-defensin-2 alleviates aflatoxin B1 induced intestinal mucosal damage via ROS-Erk1/2 signaling pathway - Qinghao Li; Man Zhang; Juan Sun; Yilei Li; Shaopo Zu; Yuqiang Xiang; Xin Jin (Science of The Total Environment, 2023)

Short-term ozone exposure and serum neural damage biomarkers in healthy elderly adults: Evidence from a panel study - Rongrong Qu; Beibei Sun; Jing Jiang; Zhen An; Juan Li; Hui Wu; Weidong Wu; Jie Song (Science of The Total Environment, 2023)

Enhancement of carbon nanotubes on microalgal-fungal consortium formation and wastewater treatment - Juan Liu; Li Liu; Shilun Wang; Shiqing Sun; Changwei Hu; Yongjun Zhao (Journal of Environmental Management, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Facilitating winter wheat sustainable intensification: Effects of two limited carbon-emission cultivation patterns in China's Huang-Huai-Hai Region - Xuechen Xiao; Juan Kang; Huawei Li; Yang Liu; Chunsheng Yao; Zhen Zhang; Ying Liu; Wan Sun; Guozhang Kang; Zhimin Wang; Chenyang Wang; Zhengbin Zhang; et al. (Agriculture, Ecosystems & Environment, 2023)

First principles insights into the interaction mechanism of iron doped thermally activated kaolinite with Cd and Pb pollutants in organic solid waste incineration flue gas - Yang-wen Wu; Rong Guo; Li-juan Sun; Xin-yue Zhou; Jia-le Zhou; Hai-yuan Zhao; Yi-fei Yu; Zhuang Hu; Bin Hu; Ji Liu; Bing Zhang; Li Zhao; et al. (Waste Management, 2023)

Interactions between microplastics and contaminants: A review focusing on the effect of aging process - Hongwei Luo; Chaolin Tu; Dongqin He; Anping Zhang; Jianqiang Sun; Jun Li; Juan Xu; Xiangliang Pan (Science of The Total Environment, 2023)

Effect of soil spatial aggregation caused by the calculation unit division on runoff and sediment load simulation in the SWAT model - Juan Xiao; Yao Wang; Jinxing Sun; Shuishi Xie; Yan Huang; Zhiwei Wan; Lihong Meng; Xiujuan Li; Keyuan Zhong (Journal of Hydrology, 2023)

Delayed sowing increased dry matter accumulation during stem elongation in winter wheat by improving photosynthetic yield and nitrogen accumulation - Yuangang Zhu; Juan Liu; Jiaqi Li; Lishan Xian; Jinpeng Chu; Hui Liu; Jian Song; Yinghui Sun; Zhongmin Dai (European Journal of Agronomy, 2023)

Short-term changes in soil labile carbon and nitrogen pools with biochar application in a suburban native forest in subtropical Australia - Jiaping Yang; Juan Zhan; Sabah Taresh; Weiling Sun; Yinan Li; Ashrafun Nessa; Qinggui Wu; Zhihong Xu (Journal of Soils and Sediments, 2023)

Modification of Fruit Quality and Leaf Mineral Composition of ‘Nagafu No.2’ Apple Grafted onto Four Dwarfing Interstocks - Yanmei Li; Zonghuan Ma; Yanbiao Li; Wenfang Li; Lulong Sun; Jutao Xu; Juan Mao; Baihong Chen (Journal of Plant Growth Regulation, 2023)

Effects of light quality, nitrogen source and Fe3+ concentration on female gametophyte development of Costaria costata - Shuxiu Chen; Xiaojie Li; Juan Sun; Xia Li; Nan Zhao; Liang Shi (Aquatic Botany, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Driver of eustatic change during the early Aptian Oceanic Anoxic Event 1a (∼120 Ma) - Yiwei Xu; Xiumian Hu; Eduardo Garzanti; Gaoyuan Sun; Jingxin Jiang; Juan Li; Shijie Zhang; Felix Schlagintweit (Global and Planetary Change, 2023)

Expression profiles of circular RNAs in spermatozoa from aging men - Qiao Zhou; Anming Liu; Hui Ji; Juan Ji; Jingwen Sun; Zhonghui Ling; Guangyao Li; Xiufeng Ling; Lu xu; Xiaoning Chen (Molecular Biology Reports, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Comprehensive transcriptome and metabolome analysis reveals regulatory network for lignin biosynthesis in chicory sprouting - Juan Li; Xiaozhu Guo; Gui Wang; Zhenjie Zhou; Xuemei Sun (Plant Biotechnology Reports, 2023)

A novel approach using multispectral imaging for rapid development of seed pellet formulations to mitigate drought stress in alfalfa - Zhicheng Jia; Chengming Ou; Shoujiang Sun; Juan Wang; Jingyu Liu; Manli Li; Shangang Jia; Peisheng Mao (Computers and Electronics in Agriculture, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Carbonate factories and their critical control on the geometry of carbonate platforms (mid-Cretaceous, southern Iran) - Yiwei Xu; Xiumian Hu; Eduardo Garzanti; Gaoyuan Sun; Jingxin Jiang; Juan Li; Shijie Zhang; Felix Schlagintweit; Xin Rao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Seasonal–interannual–decadal variations of sea level in the South China Sea and connections with the tropical–subtropical Pacific - Juan Li; Wei Tan; Wenjin Sun; Lina Yang; Lei Lin; Qingjun Fu (International Journal of Climatology, 2023)
Different timescale contributions to the sea‐level variation in the South China Sea (SCS) are evaluated in this paper. On seasonal timescale, the large variance of the sea‐level anomaly (SLA) could account for more than 70% of the monthly sea‐level variation in the western shallow continental shelf and the area of Luzon cold eddy. Besides, the seasonal explained variance percentage (skill) has 2 weak centres (50%–70%) off eastern Vietnam, which is related to the summertime eddy pair in the SCS. On interannual‐to‐decadal (low‐frequency) timescale, the skill has two large‐value regions (Zone A and Zone B). Zone A is characterized by double centres off eastern Vietnam, but the meridional position of the double centres is farther north than that of the eddy pair. The skill in Zone A is in the range of 35%–55%, and about 50%–70% of the low‐frequency variation comes from the steric effect. Zone B is off the west coast of the Philippines. The skill in Zone B increases southward, and it is dominated by the wind‐induced dynamic process which is attributed to the remote Rossby wave from the tropical Pacific. Based on the S‐EOF analysis, the SEOF‐1 mode mainly portrays the decadal variation of the SLA, while the SEOF‐2 mode reflects the interannual variation of the SLA. In Zone B, almost all of the low‐frequency variation could be attributed to ENSO and PDO, especially to PDO which has a larger contribution. However, the double centres in Zone A are governed by the SCS summer monsoon, instead of ENSO and PDO.

Molecular-level exploration of properties of dissolved organic matter in natural and engineered water systems: A critical review of FTICR-MS application - Mingqi Ruan; Fengchang Wu; Fuhong Sun; Fanhao Song; Tingting Li; Chen He; Juan Jiang (Critical Reviews in Environmental Science and Technology, 2023)

Fingerprint characteristics of refined oils and their traceability in the groundwater environment - Juan Sun; Xiaoyang Wang; Quanwei Song; Ran Li; Jiacai Xie; Xiaoqing Yang; Liuping Cai; Zihao Wang; Chaocheng Zhao; Xiuxia Zhang (Chemosphere, 2023)

Identification of new conserved linear B-cell epitopes in the 3AB and 3C protein of Senecavirus A - Jian Li; Junfang Yan; Yanni Gao; Xing Liu; Haifeng Sun; Juan Bai; Ping Jiang (Veterinary Microbiology, 2023)

Soil pollution and the invasion of congener Sphagneticola in crop lands - Qaiser Javed; Jianfan Sun; Susan Rutherford; Juan Li; Babar Iqbal; Yan Xiang; Guangqian Ren; Feng He; Linxuan Pan; Yanwen Bo; Wajid Ali Khattak; Daolin Du (Journal of Environmental Management, 2023)

A method to estimate leaf area index from VIIRS surface reflectance using deep transfer learning - Juan Li; Zhiqiang Xiao; Rui Sun; Jinling Song (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The Mechanism of Immobilization of Cd(II) by Phosphate-Solubilizing Bacteria Bacillus sp. B19 - Si-Yi Liu; Qiang Pu; Tian-Jin Mo; Guixiang Peng; Yan Sun; Yulong Zhang; Jinjin Wang; Yongtao Li; Hui-Juan Xu (Water, Air, & Soil Pollution, 2023)

A spike-trimer protein-based tetravalent COVID-19 vaccine elicits enhanced breadth of neutralization against SARS-CoV-2 Omicron subvariants and other variants - Rui Wang; Hongpeng Huang; Chulin Yu; Chunyun Sun; Juan Ma; Desheng Kong; Yalong Lin; Dandan Zhao; Shaozheng Zhou; Jianbo Lu; Sai Cao; Yanjing Zhang; et al. (Science China Life Sciences, 2023)

Microbiota of a seepage face at the mouth of a subterranean estuary: diversity, distribution and substrate dependence - Yueming Wu; Yongjun Wei; Juan Severino Pino Ibánhez; Danqing Sun; Kaiqi Lu; Qianqian Wang; Jian Li; Shan Jiang (Acta Oceanologica Sinica, 2023)

Marine oil spill remediation by Candelilla wax modified coal fly ash cenospheres - Juan Sun; Ran Li; Xiaoyang Wang; Chaocheng Zhao; Quanwei Song; Fang Liu; Zihao Wang; Chunshuang Liu; Xiuxia Zhang (Chemosphere, 2023)

A novel kneading method for improving the quality of whole wheat dough and bread - Juan Sun; Waleed AL-Ansi; Fan Zhu; Mingcong Fan; Yan Li; Haifeng Qian; Li Wang (Journal of Cereal Science, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

Effects of tri-n-butyl phosphate (TnBP) on neurobehavior of Caenorhabditis elegans - Jielin Tang; Jinyan Qin; Guzailinuer Kuerban; Jiayi Li; Qinyu Zhou; Hongdan Zhang; Rongli Sun; Lihong Yin; Yuepu Pu; Juan Zhang (Environmental Science and Pollution Research, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Corrigendum to “Mechanism of PM2.5-induced human bronchial epithelial cell toxicity in central China” [J Hazard Mater 396 (2020) 122747] - Shuyin Duan; Meihua Zhang; Yaqiong Sun; Zhenya Fang; Hefeng Wang; Shuxian Li; Yanze Peng; Juan Li; Junxia Li; Jiaqi Tian; Haoyu Yin; Sanqiao Yao; et al. (Journal of Hazardous Materials, 2023)

Microplastics exhibit accumulation and horizontal transfer of antibiotic resistance genes - Yue Feng; Jia-Wen Sun; Wei-Wei Shi; Jian-Lu Duan; Xiao-Dong Sun; Li-Juan Feng; Qian Wang; Yu-Dong Gan; Xian-Zheng Yuan (Journal of Environmental Management, 2023)

Distribution characteristics of photoinitiators and their flux estimation from the Pearl River Delta to the coastal waters of the South China Sea - Yuqing He; Zibin Pan; Xinxin Liang; Ruiman Xie; Yuying Sun; Juan Li; Yawei Wang; Lixi Zeng (Journal of Environmental Sciences, 2023)

Synergistic double doping of Co and Cu constructs multiple active sites to achieve catalyzed degradation of toluene at high humidity - Min Xu; Lei Wang; Yonggang Sun; Yulong Ma; Li Zhu; Yingbo Zhu; Juan Zhang; Song Qiao; Jingdan Gao; Wenxin Ji; Yuanyuan Li (Fuel, 2023)

Precise regulation of built-in electric field over NH2-MIL-125-Ti/WO3-x S-scheme heterojunction for achieving simultaneous formation of CO and H2O2 from CO2 and H2O - Haopeng Jiang; Lele Wang; Xiaohui Yu; Lijuan Sun; Jinhe Li; Juan Yang; Qinqin Liu (Chemical Engineering Journal, 2023)

Will extreme temperature events emerge earlier under global warming? - Jinxing Sun; Ting Liu; Shuishi Xie; Juan Xiao; Li Huang; Zhiwei Wan; Keyuan Zhong (Atmospheric Research, 2023)

Low-rate ferrate dosing damages the microbial biofilm structure through humic substances destruction and facilitates the sewer biofilm control - Xiaofang Yan; Jing Sun; Yizhen Wang; Zisha Zhang; Chuning Zhang; Wei Li; Juan Xu; Xiaohu Dai; Bing-Jie Ni (Water Research, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Fluid evolution and ore genesis of the A'gui Cu deposit in southern Great Xing'an Range, Northeast China: Evidence from fluid inclusion and C–H–O–S–Pb isotopes - Xue Wang; Ke-yong Wang; Li-juan Fu; Qing-ying Zhao; Qing-fei Sun; Chao Zhang (Geochemistry, 2023)

An integrated electrolysis-microfiltration-ion exchange closed-loop system for effective water softening without chemicals input and spent regenerant discharge - Xuchen Ba; Jinghua Chen; Xuesong Wang; Hao Xu; Junqiang Sun; Yuanfeng Qi; Yifan Li; Juan Wang; Bo Jiang (Desalination, 2023)

Characterization of RING-type ubiquitin SINA E3 ligases and their responsive expression to salt and osmotic stresses in Brassica napus - Fengyan Fang; Wenlong Zhou; Yanfeng Liu; Zhizhong Song; Songfeng Zheng; Fei Wang; Zeyu Lu; Dazhuang Qi; Bei Li; Nan Sun; Xiaoli Tang; Juan Zhang; et al. (Plant Cell Reports, 2023)

Metabolomics analysis reveals cytotoxic effects of ouabain towards psoriatic keratinocytes via impairment of glutathione metabolism - Xuan Zhou; Fei Fei; Wei Song; Hehua Ma; Zhenzhen Xu; Jing Yue; Bei Cao; Runbin Sun; Yu Zhao; Yuanxun Yang; Junyi Jiang; Yan Geng; et al. (Molecular Genetics and Genomics, 2023)
Ouabain is a cardiac glycoside long studied for treating heart diseases, but the attempts to evaluate its anti-psoriatic activity have not been reported. We aimed to explore the effects of ouabain on proliferation and metabolism towards psoriatic keratinocytes. In human HaCaT keratinocytes, ouabain potently decreased viability, promoted apoptosis and caused G2/M cycle arrest. Metabolomics analysis indicated that ouabain markedly impaired glutathione metabolism. The solute carrier family 7 member 11 (SLC7A11) is an amino acid transporter highly specific to cysteine, which is critical for glutathione synthesis. Ouabain downregulated SLC7A11, reduced cysteine uptake and subsequently inhibited glutathione synthesis, probably through inhibiting Akt/mTOR/beclin axis that regulate protein activity of SLC7A11. The impaired glutathione synthesis and oxidative stress caused by ouabain may contribute to its cytotoxicity towards psoriatic keratinocytes. Our results provide experimental evidence supporting further study of ouabain as a potential anti-psoriatic agent.

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

The foundering of stagnant slabs bearing oceanic plateau into the lower mantle - Xi Liu; Juan Li; Zhigang Zhang; Weidong Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Polyvinyl alcohol/montmorillonite/magnesium diboride fibers with superior flame retardancy, strength, and flexibility - Wei Wang; Juan He; Chunlin Li; Nan Zhang; Xuexia He; Qi Li; Jie Sun; Ruibing Jiang; Zhibin Lei; Zong-Huai Liu (Chemical Engineering Journal, 2023)

Effects of mowing on Pb accumulation and transport in Cynodon dactylon (L.) Pers - Xinyi Cai; Xi Li; Lingli Peng; Yahao Liang; Mingyan Jiang; Jun Ma; Lingxia Sun; Baimeng Guo; Xiaofang Yu; Juan Du; Nian Li; Shizhen Cai (Environmental Science and Pollution Research, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Electrospun nanofibres containing Zn-MOF for electrochemiluminescent determination of fenpropathrin residues in fruit juices - Zhuo Sun; Juan Lu; Xin Zhang; Xiangyu Shan; Qian Wu; Chao Li; Huiling Li; Shuning Yang; Li Tian (Food Chemistry, 2023)

Divergent effects of moderate grazing duration on carbon sequestration between temperate and alpine grasslands in China - Zhenchao Zhang; Ting Hua; Yanhua Zhao; Yanpeng Li; Yi Wang; Fei Wang; Juan Sun; Jian Sun (Science of The Total Environment, 2023)

Microplastics induce neurotoxicity in aquatic animals at environmentally realistic concentrations: A meta-analysis - Fei Xiong; Jinyan Liu; Kai Xu; Jiawei Huang; Daqin Wang; Fuxian Li; Shiyuan Wang; Juan Zhang; Yuepu Pu; Rongli Sun (Environmental Pollution, 2023)

A ratiometric fluorescent biosensing strategy based on a composite nanoplatform and dual signal amplification for exosomal miRNA detection - Zhiwei Sun; Juan Li; Yao Tong; Yufei Yang; Hui Li; Chuanxin Wang; Lutao Du; Yanyan Jiang (Chemical Engineering Journal, 2023)

The oxidation mechanism and kinetics of limononic acid by hydroxyl radical in atmospheric aqueous phase - Yanqi Chen; Guochun Lv; Yan Wang; Xiaofan Li; Juan Sun; Xuehua Zhou; Xiaomin Sun (Atmospheric Environment, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Effects of mold, water damage and window pane condensation on adult rhinitis and asthma partly mediated by different odors - Juan Wang; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Chen Huang; Xin Zhang; Qihong Deng; Chan Lu; Hua Qian; Xu Yang; Yuexia Sun; Dan Norbäck (Building and Environment, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Aaptamine derivatives with CDK2 inhibitory activities from the South China Sea sponge Aaptos suberitoides - Qian-Qian He; Yu-Qing Man; Kun-Lai Sun; Li-Juan Yang; Yan Wu; Jing Du; Wei-Wei Chen; Juan-Juan Dai; Na Ni; Shuang Miao; Kai-Kai Gong (Natural Product Research, 2022)

Correction to: Behavioral and brain functional characteristics of children with attention-defcit/hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Behavioral and brain functional characteristics of children with Attention-Deficit/Hyperactivity disorder and anxiety trait - Zhao-Min Wu; Peng Wang; Juan Liu; Lu Liu; Xiao-Lan Cao; Li Sun; Qing-Jiu Cao; Li Yang; Yu-Feng Wang; Bin-Rang Yang (Brain Imaging and Behavior, 2022)

Bioremediation of petroleum hydrocarbon contaminated soil by microorganisms immobilized on sludge modified by non-ionic surfactant - Junlong Yu; Ruyue Li; Xiuxia Zhang; Yi Du; Ruojun Ma; Xiaodong Zhao; Shuai Zuo; Kangning Dong; Ruirui Wang; Yupeng Zhang; Yingying Gu; Juan Sun (Environmental Science and Pollution Research, 2022)

Correction to: Soybean genetic resources contributing to sustainable protein production - Bingfu Guo; Liping Sun; Siqi Jiang; Honglei Ren; Rujian Sun; Zhongyan Wei; Huilong Hong; Xiaoyan Luan; Jun Wang; Xiaobo Wang; Donghe Xu; Wenbin Li; et al. (Theoretical and Applied Genetics, 2022)

Soybean genetic resources contributing to sustainable protein production - Bingfu Guo; Liping Sun; Siqi Jiang; Honglei Ren; Rujian Sun; Zhongyan Wei; Huilong Hong; Xiaoyan Luan; Jun Wang; Xiaobo Wang; Donghe Xu; Wenbin Li; et al. (Theoretical and Applied Genetics, 2022)
Key message Genetic resources contributes to the sustainable protein production in soybean. Abstract Soybean is an important crop for food, oil, and forage and is the main source of edible vegetable oil and vegetable protein. It plays an important role in maintaining balanced dietary nutrients for human health. The soybean protein content is a quantitative trait mainly controlled by gene additive effects and is usually negatively correlated with agronomic traits such as the oil content and yield. The selection of soybean varieties with high protein content and high yield to secure sustainable protein production is one of the difficulties in soybean breeding. The abundant genetic variation of soybean germplasm resources is the basis for overcoming the obstacles in breeding for soybean varieties with high yield and high protein content. Soybean has been cultivated for more than 5000 years and has spread from China to other parts of the world. The rich genetic resources play an important role in promoting the sustainable production of soybean protein worldwide. In this paper, the origin and spread of soybean and the current status of soybean production are reviewed; the genetic characteristics of soybean protein and the distribution of resources are expounded based on phenotypes; the discovery of soybean seed protein-related genes as well as transcriptomic, metabolomic, and proteomic studies in soybean are elaborated; the creation and utilization of high-protein germplasm resources are introduced; and the prospect of high-protein soybean breeding is described.

Exploring the Oxidative Stress Regulation of Mice with Hyperglycemia by Lactiplantibacillus plantarum SCS4 - Xiao Meng; Xin-Zhi Chen; Jia-Yi Sun; Ying Zhang; Li-Shi Jiang; Juan Wang (Current Microbiology, 2022)

Four new secoiridoids from the stem barks of Syringa reticulata (Bl.) Hara - Shuang Guo; Yan Liu; Yan-Ping Sun; Juan Pan; Wei Guan; Xiao-Mao Li; Si-Yi Wang; Adnan Mohammed Algradi; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Associations of long-term ambient air pollution and traffic-related pollution with blood pressure and hypertension defined by the different guidelines worldwide: the CHCN-BTH study - Bingxiao Li; Han Cao; Kuo Liu; Juan Xia; Yanyan Sun; Wenjuan Peng; Yunyi Xie; Chunyue Guo; Xiaohui Liu; Fuyuan Wen; Fengxu Zhang; Guangliang Shan; et al. (Environmental Science and Pollution Research, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Two new terpenes from the aerial parts of Clematis chinensis Osbeck - Sun Ye; Liu Yan; Yan-Ping Sun; Xiao-Mao Li; Wang Si-Yi; Juan Pan; Wei Guan; Yuan Liu; Anam Naseem; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Four new polyacetylenes from the roots of Saposhnikovia divaricata - Yan Sun; Yan-Ping Sun; Yan Liu; Juan Pan; Wei Guan; Xiao-Mao Li; Yuan Liu; Anam Naseem; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

Citrus flavonoids and their antioxidant evaluation - Yue Wang; Xiao-Juan Liu; Jie-Biao Chen; Jin-Ping Cao; Xian Li; Chong-De Sun (Critical Reviews in Food Science and Nutrition, 2022)

Transcriptome Analysis of Sophora davidii Leaves in Response to Low-Phosphorus Stress - Xin Zhao; Li-Juan Huang; Li-Li Zhao; Pu-Chang Wang; Xiao-Fu Sun (Journal of Plant Growth Regulation, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Influence of the NAO on Wintertime Surface Air Temperature over East Asia: Multidecadal Variability and Decadal Prediction - Jianping Li; Tiejun Xie; Xinxin Tang; Hao Wang; Cheng Sun; Juan Feng; Fei Zheng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2022)
In this paper, we investigate the influence of the winter NAO on the multidecadal variability of winter East Asian surface air temperature (EASAT) and EASAT decadal prediction. The observational analysis shows that the winter EASAT and East Asian minimum SAT (EAmSAT) display strong in-phase fluctuations and a significant 60–80-year multidecadal variability, apart from a long-term warming trend. The winter EASAT experienced a decreasing trend in the last two decades, which is consistent with the occurrence of extremely cold events in East Asia winters in recent years. The winter NAO leads the detrended winter EASAT by 12–18 years with the greatest significant positive correlation at the lead time of 15 years. Further analysis shows that ENSO may affect winter EASAT interannual variability, but does not affect the robust lead relationship between the winter NAO and EASAT. We present the coupled oceanic-atmospheric bridge (COAB) mechanism of the NAO influences on winter EASAT multidecadal variability through its accumulated delayed effect of ∼15 years on the Atlantic Multidecadal Oscillation (AMO) and Africa–Asia multidecadal teleconnection (AAMT) pattern. An NAO-based linear model for predicting winter decadal EASAT is constructed on the principle of the COAB mechanism, with good hindcast performance. The winter EASAT for 2020–34 is predicted to keep on fluctuating downward until ∼2025, implying a high probability of occurrence of extremely cold events in coming winters in East Asia, followed by a sudden turn towards sharp warming. The predicted 2020/21 winter EASAT is almost the same as the 2019/20 winter.

Effects of ambient temperature on outpatient visits for dermatitis in Xinxiang, China: a time-series analysis - Ling Chao; Yajun Sun; Zhen An; Juan Li; Weidong Wu; Yue Liu; Jie Song (Environmental Science and Pollution Research, 2022)

A 250 m resolution global leaf area index product derived from MODIS surface reflectance data - Zhiqiang Xiao; Jinling Song; Hua Yang; Rui Sun; Juan Li (International Journal of Remote Sensing, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Nutrient and tetracycline removal from simulated biogas slurry and biogas upgrading by microalgae cultivation under different carbon nanotubes concentrations - Li Sun; Chunzhi Zhao; Shiqing Sun; Changwei Hu; Yongjun Zhao; Juan Liu (Environmental Science and Pollution Research, 2022)

East Asian summer monsoon changes in subtropical China since late Pleistocene: Evidence from the Ailuropoda-Stegodon fauna - Zhi-wen Li; Li Sun; Bao-sheng Li; Feng-nian Wang; Ding-ding Du; You-gui Song; Hui-Juan Zhang; Liu-qin Chen; Dan Xu (Journal of Mountain Science, 2022)

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Seven new glycosides from the leaves of Datura metel L. - Jin-Yan Tan; Yan Liu; Yan-Gang Cheng; Yan-Ping Sun; Xiao-Mao Li; Wei Guan; Juan Pan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Transcriptome analysis reveals differing response and tolerance mechanism of EPSPS and GAT genes among transgenic soybeans - Bing-Fu Guo; Hui-Long Hong; Li-Ping Sun; Yong Guo; Li-Juan Qiu (Molecular Biology Reports, 2021)

24-epibrassinolide enhanced cold tolerance of winter turnip rape (Brassica rapa L.) - Yao Li; Yuanpei Sun; Cheng Ma; Xin Kang; Juan Wang; Tengguo Zhang (Biologia, 2021)

Functional Near-Infrared Spectroscopy Neurofeedback of Cortical Target Enhances Hippocampal Activation and Memory Performance - Xin Hou; Xiang Xiao; Yilong Gong; Yihan Jiang; Peipei Sun; Juan Li; Zheng Li; Xiaojie Zhao; Li Yao; Antao Chen; Chaozhe Zhu (Neuroscience Bulletin, 2021)

MiR-137 regulates low-intensity shear stress–induced human aortic endothelial cell apoptosis via JNK/AP-1 signaling - Guo-jian Li; Qiong-hui Yang; Guo-kai Yang; Jia Wan; Ling-juan Du; Zhao-xiang Li; Yi Sun (Journal of Physiology and Biochemistry, 2021)

Determination of Deoxynivalenol and Its Derivative in Corn Flour and Wheat Flour Using Automated On-line Solid-Phase Extraction Combined with LC–MS/MS - Meirong Cao; Qiang Li; Yan Zhang; Juan Wang; Hongwen Zhai; Junmei Ma; Lei Sun; Xianghong Wan; Yiwei Tang (Bulletin of Environmental Contamination and Toxicology, 2021)

Response of growth characteristics and endogenous hormones of Sophora davidii to low-phosphorus stress - Xin Zhao; Li-Li Zhao; Li-Juan Huang; Xiao-Fu Sun; Pu-Chang Wang (Acta Physiologiae Plantarum, 2021)

De novo hydroponics system efficiency for the cuttings of alfalfa (Medicago sativa L.) - Zhili Zhao; Wenyu Zhang; Yang Liu; Shuai Li; Wu Yao; Xiaohui Sun; Siyu Li; Lichao Ma; Juan Sun; Qingchuan Yang; Yongxiang Li; Guofeng Yang; et al. (Physiology and Molecular Biology of Plants, 2021)
The legume plant alfalfa ( Medicago sativa L.) is a widely cultivated perennial forage due to its high protein content, palatability, and strong adaptability to diverse agro-ecological zones. Alfalfa is a self-incompatible cross-pollinated autotetraploid species with tetrasomic inheritance. Therefore, maintaining excellent traits through seed reproduction is a prime challenge in alfalfa. However, the cutting propagation technology could enable consistent multiplication of quality plants that are genetically identical to the parent plant. The current study aimed to develop a simple, cost-effective, reproducible, and efficient hydroponic cutting method to preserve alfalfa plants and for molecular research. In this study, alfalfa landrace ‘Wudi’ was grown in hydroponics for 30 days and used as source material for cuttings. The top, middle and bottom sections of its stem were used as cuttings. The rooting rate, root length, and stem height of the different stem sections were compared to determine the best segment for alfalfa propagation in four nutrient treatments (H M , H M + 1/500H, H M + 1/1000H and d H M + 1/2000H). After 21 days of culture, the rooting rates of all the three stem types under four cutting nutrient solutions were above 78%. The rooting rate of the middle and bottom parts in H M + 1/1000 H and H M + 1/2000 H nutrient solutions reached more than 93%, with a higher health survey score (> 4.70). In conclusion, this study developed a de novo cutting propagation method that can be used to conserve and propagate germplasm in breeding programs and research. This method is a new report on the cutting propagation of alfalfa by hydroponics, which could supplement the existing cutting propagation methods.

Identification of novel catabolic genes involved in 17 β ‐estradiol degradation by Novosphingobium sp. ES2 ‐1 - Shunyao Li; Kai Sun; Xin Yan; Chao Lu; Michael Gatheru Waigi; Juan Liu; Wanting Ling (Environmental Microbiology, 2021)
Summary Novosphingobium sp. ES2‐1 is an efficient 17 β ‐estradiol (E2)‐degrading bacterium, which can convert E2 to estrone (E1), then to 4‐hydroxyestrone (4‐OH‐E1) for subsequent oxidative cracking. In this study, the molecular bases for this process were elucidated. Two novel monooxygenase systems EstP and EstO were shown to catalyse the oxygenation of E1 and 4‐OH‐E1, respectively. EstP was a three‐component cytochrome P450 monooxygenase system consisting of EstP1 (P450 monooxygenase), EstP2 (ferredoxin) and EstP3 (ferredoxin reductase). Ultraperformance liquid chromatography‐high resolution mass spectrometry (UPLC‐HRMS) analysis revealed that EstP catalysed the 4‐hydroxylation of E1 to produce 4‐OH‐E1. The resultant 4‐OH‐E1 was further oxidized by a two‐component monooxygenase system EstO consisting of EstO1 (flavin‐dependent monooxygenases) and EstO2 (flavin reductase). UPLC‐HRMS combined with 1 H‐nuclear magnetic resonance analysis demonstrated that EstO catalysed the breakage of C9‐C10 to yield a ring B‐cleavage product. In addition, the oxygenase component genes estP1 and estO1 exhibited contrary inductive behaviours when exposed to different steroids, suggesting that EstP1‐mediated 4‐hydroxylation was E2‐specific, whereas EstO1‐mediated monooxygenation might be involved in the degradation of testosterone, androstenedione, progesterone and pregnenolone. This also implied that the mechanisms of the catabolism of different steroids by the same microorganism might be partially interlinked.

Effects of Spray Parameters on the Effective Spray Width of Single-Rotor Drone in Sugarcane Plant Protection - Ping Zhang; Wei Zhang; Hai-Tian Sun; Feng-Guang He; Hai-Ba Fu; Li-Qiang Qi; Li-Juan Yu; Li-Yu Jin; Bo Zhang; Jian-Sheng Liu (Sugar Tech, 2021)

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

A new method for dividing the scopes and priorities of air pollution control based on environmental justice - Liwen Sun; Juan Du; Yifan Li (Environmental Science and Pollution Research, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Molecular characterization of structural protein genes of dengue virus serotype 1 epidemic in Yunnan, Southwest China, in 2018 - Qingping Lan; Yun Shu; Linhao Li; Xiyun Shan; Dehong Ma; Tingting Li; Xiaodan Wang; Yue Pan; Junying Chen; Juan Zhang; Pinghua Liu; Qiangming Sun (Archives of Virology, 2021)

Least-squares reverse time migration method using the factorization of the Hessian matrix - Sun Xiao-Dong; Teng Hou-Hua; Ren Li-Juan; Wang Wei-Qi; Li Zhen-Chun (Applied Geophysics, 2021)

Moving Window Method: An Effective Approach to Measure Surrounding Greenness - Qingyan Meng; Yunxiao Sun; Xu Chen; Juan Li; Xuemiao Wang; Jun Wu (Journal of the Indian Society of Remote Sensing, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

The mRNA expression of ompF, invA and invE was associated with the ciprofloxacin-resistance in Salmonella - Xiongwei Du; Ying Liu; Xiaojie Sun; Jianmei Zhao; Juan Wang; Jianping Li; Xuelian Liu; Junwei Wang; Ye Li (Archives of Microbiology, 2020)

Does CMIP6 Inspire More Confidence in Simulating Climate Extremes over China? - Huanhuan Zhu; Zhihong Jiang; Juan Li; Wei Li; Cenxiao Sun; Laurent Li (Advances in Atmospheric Sciences, 2020)

Gnaq Protects PC12 Cells from Oxidative Damage by Activation of Nrf2 and Inhibition of NF-kB - Xin Sun; Guo-Ping Li; Pu Huang; Lu-Gang Wei; Jia-Zhi Guo; Li-Juan Ao; Di Lu; Shao-Chun Chen (NeuroMolecular Medicine, 2020)

Orogenic Movements during the Paleozoic Period: Development of the Granitoid Formations in the Northwestern Region of Spain’s Iberian Peninsula - Juan Ramon Vidal Romaní; Zhaojun Song; Huimin Liu; Yifang Sun; Haonan Li (Journal of Earth Science, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Using probiotics for type 2 diabetes mellitus intervention: Advances, questions, and potential - Zhongke Sun; Xuejiao Sun; Juan Li; Zhaoyang Li; Qingwei Hu; Lili Li; Xinqi Hao; Maoping Song; Chengwei Li (Critical Reviews in Food Science and Nutrition, 2020)

Enterovirus A71 capsid protein VP1 increases blood–brain barrier permeability and virus receptor vimentin on the brain endothelial cells - Wenjing Wang; Jiandong Sun; Nan Wang; Zhixiao Sun; Qiyun Ma; Jun Li; Mingshun Zhang; Juan Xu (Journal of NeuroVirology, 2020)
Enterovirus A71 (EV-A71) is the major cause of severe hand-foot-and-mouth diseases (HFMD), especially encephalitis and other nervous system diseases. EV-A71 capsid protein VP1 mediates virus attachment and is the important virulence factor in the EV-A71pathogenesis. In this study, we explored the roles of VP1 in the permeability of blood–brain barrier (BBB). Sera albumin, Evans blue, and dextran leaked into brain parenchyma of the 1-week-old C57BL/6J mice intracranially injected with VP1 recombinant protein. VP1 also increased the permeability of the brain endothelial cells monolayer, an in vitro BBB model. Tight junction protein claudin-5 was reduced in the brain tissues or brain endothelial cells treated with VP1. In contrast, VP1 increased the expression of virus receptor vimentin, which could be blocked with VP1 neutralization antibody. Vimentin expression in the VP1-treated brain endothelial cells was regulated by TGF-β/Smad-3 and NF-κB signal pathways. Moreover, vimentin over-expression was accompanied with compromised BBB. From these studies, we conclude that EV-A71 virus capsid protein VP1 disrupted BBB and increased virus receptor vimentin, which both may contribute to the virus entrance into brain and EV-A71 CNS infection.

An inter-basin teleconnection from the North Atlantic to the subarctic North Pacific at multidecadal time scales - Zhanqiu Gong; Cheng Sun; Jianping Li; Juan Feng; Fei Xie; Ruiqiang Ding; Yun Yang; Jiaqing Xue (Climate Dynamics, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Source Identification of Trace Elements in Peri-urban Soils in Eastern China - Long Sun; Manus Carey; Lei Yang; Li-Ding Chen; Shou-Juan Li; Fang-Kai Zhao; Yong-Guan Zhu; Caroline Meharg; Andrew A. Meharg (Exposure and Health, 2019)

Pathways of Influence of the Northern Hemisphere Mid-high Latitudes on East Asian Climate: A Review - Jianping Li; Fei Zheng; Cheng Sun; Juan Feng; Jing Wang (Advances in Atmospheric Sciences, 2019)

Theoretical analysis of potential applications of microwave radar for sandstorm detection - Wang Juan; Xingcai Li; Minzhong Wang; Wenhai Sun (Theoretical and Applied Climatology, 2019)

MicroRNA-132-3p represses Smad5 in MC3T3-E1 osteoblastic cells under cyclic tensile stress - MingYan Liu; Fen Sun; YunXia Feng; XinYi Sun; Juan Li; Qiang Fan; Ming Liu (Molecular and Cellular Biochemistry, 2019)

Expression patterns of alpha-amylase and beta-amylase genes provide insights into the molecular mechanisms underlying the responses of tea plants (Camellia sinensis) to stress and postharvest processing treatments - Chuan Yue; Hongli Cao; Hongzheng Lin; Juan Hu; Yijun Ye; Jiamin Li; Zhilong Hao; Xinyuan Hao; Yun Sun; Yajun Yang; Xinchao Wang (Planta, 2019)

NAO implicated as a predictor of the surface air temperature multidecadal variability over East Asia - Tiejun Xie; Jianping Li; Cheng Sun; Ruiqiang Ding; Kaicun Wang; Chuanfeng Zhao; Juan Feng (Climate Dynamics, 2019)

Structural characterisation and ACE-inhibitory activities of polysaccharide from Gastrodia elata Blume - Zhen-Yuan Zhu; Chun-Juan Chen; Hui-Qing Sun; Li-Jing Chen (Natural Product Research, 2019)

Isolation and characterization of a novel seed-specific promoter from peanut (Arachis hypogaea L.) - Cuiling Yuan; Chunjuan Li; Caixia Yan; Xiaobo Zhao; Juan Wang; Quanxi Sun; Shihua Shan (Molecular Biology Reports, 2019)

Growth, artificial seedling raising and cultivation of Sargassum confusum (Fucales, Phaeophyceae) inhabiting the coast of Shandong Peninsula, China - Jinhua Pan; Zhuangzhi Zhang; Shenhui Yu; Houwei Han; Xin Jiang; Liming Jiang; Guangjin Liang; Juan Sun; Xiaojie Li; Guanpin Yang (Journal of Applied Phycology, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Multiplex one-step real-time PCR assay for rapid simultaneous detection of velogenic and mesogenic Newcastle disease virus and H5-subtype avian influenza virus - Zhujun Zhang; Dong Liu; Jiao Hu; Wenqiang Sun; Kaituo Liu; Juan Li; Haixu Xu; Jing Liu; Lihong He; Daxiu Jiang; Min Gu; Shunlin Hu; et al. (Archives of Virology, 2019)

Streptomyces canus GLY-P2 degrades ferulic and p-hydroxybenzoic acids in soil and affects cucumber antioxidant enzyme activity and rhizosphere bacterial community - Fenghui Wu; Qinghua Shi; Xiu-Juan Wang; Zhong-Tao Sun; Wanying Wang; Xue Li; Li-Yuan Guo; Ji-Gang Bai (Plant and Soil, 2019)

Integrin-interacting protein Kindlin-2 induces mammary tumors in transgenic mice - Bing Li; Xiaochun Chi; Jiagui Song; Yan Tang; Juan Du; Xiaokun He; Xiaoran Sun; Zhenwu Bi; Yunling Wang; Jun Zhan; Hongquan Zhang (Science China Life Sciences, 2019)

The effect characteristics of temperature on stroke mortality in Inner Mongolia and globally - Wenfang Guo; Maolin Du; Dejun Sun; Nengjun Zhao; Zhihui Hao; Rina Wu; Chao Dong; Xiaoling Sun; Chunfang Tian; Liqun Gao; Hongwei Li; Di Yu; et al. (International Journal of Biometeorology, 2019)

Recovery of unstable digestion of vegetable waste by adding trace elements using the bicarbonate alkalinity to total alkalinity ratio as an early warning indicator - Dong Li; Juan Sun; Qin Cao; Yichao Chen; Xiaofeng Liu; Yi Ran (Biodegradation, 2019)

An advanced impact of Arctic stratospheric ozone changes on spring precipitation in China - Fei Xie; Xuan Ma; Jianping Li; Jinlong Huang; Wenshou Tian; Jiankai Zhang; Yongyun Hu; Cheng Sun; Xin Zhou; Juan Feng; Yun Yang (Climate Dynamics, 2018)

Bacillus methylotrophicus CSY-F1 alleviates drought stress in cucumber (Cucumis sativus) grown in soil with high ferulic acid levels - Xinwei Hou; Fenghui Wu; Xiu-Juan Wang; Zhong-Tao Sun; Yue Zhang; Ming-Tao Yang; Hongrui Bai; Songwen Li; Ji-Gang Bai (Plant and Soil, 2018)

Exploration of phenol tolerance mechanism through antioxidative responses of an evolved strain, Chlorella sp. L5 - Lin Zhou; Yizhong Yuan; Xuyang Li; Shouhua Mei; Juan Gao; Quanyu Zhao; Wei Wei; Yuhan Sun (Journal of Applied Phycology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Transcriptome analysis of wheat seedling and spike tissues in the hybrid Jingmai 8 uncovered genes involved in heterosis - Yong-jie Liu; Shi-qing Gao; Yi-miao Tang; Jie Gong; Xiao Zhang; Yong-bo Wang; Li-ping Zhang; Ren-wei Sun; Quan Zhang; Zhao-bo Chen; Xiang Wang; Cai-juan Guo; et al. (Planta, 2018)

Ectopic expression of sorbitol-6-phosphate 2-dehydrogenase gene from Haloarcula marismortui enhances salt tolerance in transgenic Arabidopsis thaliana - Jian-jie Gao; Yu-ru Sun; Bo Zhu; Ri-He Peng; Bo Wang; Li-Juan Wang; Zhen-Jun Li; Lei Chen; Quan-Hong Yao (Acta Physiologiae Plantarum, 2018)

Mutation screening of Chinese Treacher Collins syndrome patients identified novel TCOF1 mutations - Ying Chen; Luo Guo; Chen-long Li; Jing Shan; Hai-song Xu; Jie-ying Li; Shan Sun; Shao-juan Hao; Lei Jin; Gang Chai; Tian-yu Zhang (Molecular Genetics and Genomics, 2018)

Ammonium, nitrate, and urea play different roles for lipid accumulation in the nervonic acid—producing microalgae Mychonastes afer HSO-3-1 - Cheng Yuan; Kai Xu; Juan Sun; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2018)

Decadal-scale teleconnection between South Atlantic SST and southeast Australia surface air temperature in austral summer - Jiaqing Xue; Jianping Li; Cheng Sun; Sen Zhao; Jiangyu Mao; Di Dong; Yanjie Li; Juan Feng (Climate Dynamics, 2018)

Genetic and biological characterization of three poultry-origin H5N6 avian influenza viruses with all internal genes from genotype S H9N2 viruses - Kaituo Liu; Min Gu; Shunlin Hu; Ruyi Gao; Juan Li; Liwei Shi; Wenqi Sun; Dong Liu; Zhao Gao; Xiulong Xu; Jiao Hu; Xiaoquan Wang; et al. (Archives of Virology, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Chronic N-acetylcysteine treatment alleviates acute lipopolysaccharide-induced working memory deficit through upregulating caveolin-1 and synaptophysin in mice - Xianzhi Shen; Yanyun Sun; Mengwei Wang; Hui Shu; Li-Juan Zhu; Pei-Yun Yan; Jun-Fang Zhang; Xinchun Jin (Psychopharmacology, 2018)

Retraction Note to: MiR-154 Functions as a Tumor Suppressor in Glioblastoma by Targeting Wnt5a - Dongsheng Zhao; Rencong Wang; Junkang Fang; Xituan Ji; Juan Li; Xiaoyan Chen; Gangfeng Sun; Zhengjun Wang; Weiping Liu; Yangang Wang; Guang Cheng; Haining Zhen; et al. (Molecular Neurobiology, 2017)

Decadal Indian Ocean dipolar variability and its relationship with the tropical Pacific - Yun Yang; Jianping Li; Lixin Wu; Yu Kosaka; Yan Du; Cheng Sun; Fei Xie; Juan Feng (Advances in Atmospheric Sciences, 2017)

An overview on the application of advanced oxidation processes for the removal of naphthenic acids from water - Xiyan Xu; Gema Pliego; Juan A. Zazo; Shibo Sun; Patricia García-Muñoz; Li He; Jose A. Casas; Juan J. Rodriguez (Critical Reviews in Environmental Science and Technology, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Decolorization of textile dye RB19 using volcanic rock matrix immobilized Bacillus thuringiensis cells with surface displayed laccase - Juan Wan; Xiaowen Sun; Cheng Liu; Mengjun Tang; Lin Li; Hong Ni (World Journal of Microbiology and Biotechnology, 2017)

Morphologies of eumelanins from the ink of six cephalopods species measured by atomic force microscopy - Yulin Sun; Li Tian; Jing Wen; Juan Zhao; Wei Zhang; Chunyao Xie; Meiqing Zhou; Xiaoying Qiu; Daohai Chen (Journal of Ocean University of China, 2017)

RETRACTED ARTICLE: MiR-154 Functions as a Tumor Suppressor in Glioblastoma by Targeting Wnt5a - Dongsheng Zhao; Rencong Wang; Junkang Fang; Xituan Ji; Juan Li; Xiaoyan Chen; Gangfeng Sun; Zhengjun Wang; Weiping Liu; Yangang Wang; Guang Cheng; Haining Zhen; et al. (Molecular Neurobiology, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

Histological evidence that metformin reverses the adverse effects of diabetes on orthodontic tooth movement in rats - Jing Sun; Juan Du; Wei Feng; Boyao Lu; Hongrui Liu; Jie Guo; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

Inhibitory effect of estrogen receptor beta on P2X3 receptors during inflammation in rats - Qian Jiang; Wen-xin Li; Jia-run Sun; Tian-tian Zhu; Juan Fan; Li-hua Yu; Geoffrey Burnstock; Hua Yang; Bei Ma (Purinergic Signalling, 2017)

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

Gene expression signatures for phlegm-dampness constitution of Chinese medicine - Lingru Li; Juan Feng; Haiqiang Yao; Lan Xie; Yu Chen; Lingling Yang; Shujuan Hou; Shipeng Zhao; Ranran Sun; Yanling Wu; Tongtong Bai; Yingshuai Li; et al. (Science China Life Sciences, 2017)

Histochemical examination of the effects of high-dose 1,25(OH)2D3 on bone remodeling in young growing rats - Jing Sun; Bao Sun; Wei Wang; Xiuchun Han; Hongrui Liu; Juan Du; Wei Feng; Bo Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Pathogenicity comparison between highly pathogenic and NADC30-like porcine reproductive and respiratory syndrome virus - Zhe Sun; Juan Wang; Xiaofei Bai; Guobiao Ji; He Yan; Yingying Li; Yuzhou Wang; Feifei Tan; Yan Xiao; Xiangdong Li; Kegong Tian (Archives of Virology, 2016)

Characterization of genome-wide microsatellites of Saccharina japonica based on a preliminary assembly of Illumina sequencing reads - Linan Zhang; Jie Peng; Xiaojie Li; Cuiju Cui; Juan Sun; Guanpin Yang (Journal of Ocean University of China, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

The effect of calcitriol on high mobility group box 1 expression in periodontal ligament cells during orthodontic tooth movement in rats - Jian Cui; Juan Li; Wei Wang; Xiuchun Han; Juan Du; Jing Sun; Wei Feng; Bo Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Effect of Boric Acid Supplementation on the Expression of BDNF in African Ostrich Chick Brain - Juan Tang; Xing-ting Zheng; Ke Xiao; Kun-lun Wang; Jing Wang; Yun-xiao Wang; Ke Wang; Wei Wang; Shun Lu; Ke-li Yang; Peng-Peng Sun; Haseeb Khaliq; et al. (Biological Trace Element Research, 2016)

The characteristics of rill development and their effects on runoff and sediment yield under different slope gradients - Ji-jun He; Li-ying Sun; Hui-li Gong; Qiang-guo Cai; Li-Juan Jia (Journal of Mountain Science, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Phylogenetic and biological characterization of three K1203 (H5N8)-like avian influenza A virus reassortants in China in 2014 - Juan Li; Min Gu; Dong Liu; Benqi Liu; Kaijun Jiang; Lei Zhong; Kaituo Liu; Wenqi Sun; Jiao Hu; Xiaoquan Wang; Shunlin Hu; Xiaowen Liu; et al. (Archives of Virology, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Simulation of the equatorially asymmetric mode of the Hadley circulation in CMIP5 models - Juan Feng; Jianping Li; Jianlei Zhu; Fei Li; Cheng Sun (Advances in Atmospheric Sciences, 2015)

Transdifferentiation of bone marrow-derived mesenchymal stem cells into salivary gland-like cells using a novel culture method - Liang Liang; Jun Wang; Yuming Zhang; Zhiyuan Shen; Jun Zheng; Jianhu Li; Zhongping Su; Juan Cai; Wei Jiang; Moyi Sun (Biotechnology Letters, 2015)

Amanita subpallidorosea, a new lethal fungus from China - Hai-Jiao Li; Jian-Wei Xie; Shuo Zhang; Ya-Juan Zhou; Pei-Bin Ma; Jing Zhou; Cheng-Ye Sun (Mycological Progress, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Histochemical evidence of zoledronate inhibiting c-src expression and interfering with CD44/OPN-mediated osteoclast adhesion in the tibiae of mice - Hongrui Liu; Jian Cui; Jing Sun; Juan Du; Wei Feng; Bao Sun; Juan Li; Xiuchun Han; Bo Liu; Yimin; Kimimitsu Oda; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Altered distribution of HMGB1 in the periodontal ligament of periostin-deficient mice subjected to Waldo’s orthodontic tooth movement - Juan Li; Wei Feng; Bo Liu; Bao Sun; Xiuchun Han; Juan Du; Jing Sun; Yimin; Jian Cui; Jie Guo; Akira Kudo; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats - Hengbo Shi; Jiangjiang Zhu; Jun Luo; Wenting Cao; Huaiping Shi; Dawei Yao; Jun Li; Yuting Sun; Huifen Xu; Kang Yu; Juan J. Loor (Functional & Integrative Genomics, 2015)

Morphological alterations of all stages of spermatogenesis and acrosome reaction in Chinese mitten crab Eriocheir sinensis - Yuan-Li Wang; Wen-Juan Sun; Lin He; Qing Li; Qun Wang (Cell and Tissue Research, 2015)

Unveiling equal importance of two 14‐3‐3 proteins for morphogenesis, conidiation, stress tolerance and virulence of an insect pathogen - Qian Liu; Jin‐Gen Li; Sheng‐Hua Ying; Juan‐Juan Wang; Wen‐Liang Sun; Chao‐Guang Tian; Ming‐Guang Feng (Environmental Microbiology, 2015)
Summary Two conserved 14‐3‐3 proteins orthologous to S accharomyces cerevisiae Bmh 1/2 are poorly understood in filamentous fungi. Here we show that Bmh 1 and Bmh 2 contribute equally to the fundamental biology and physiology of B eauveria bassiana by targeting many sets of proteins/enzymes. Single Bmh deletion caused similar upregulation of another. Excellent knockdown (∼91%) expressions of Bmh 1 in Δ Bmh 2 and Bmh 2 in Δ Bmh 1 resulted in equally more severe multiphenotypic defects than the single deletions, including G 2 / M transition, blastospore size, carbon/nitrogen utilization, conidiation, germination and conidial tolerances to high osmolarity, oxidation, cell wall stress, high temperature and UV ‐ B irradiation. All the deletion and deletion/knockdown mutants showed similar defects in blastospore yield and density, hyphal septation and cell size, hyphal responses to most chemical stresses and virulence. All the defects were evident with altered transcripts of phenotype‐related genes and well restored by each Bmh complementation. Our Bmh 1 ‐ and Bmh 2 ‐specific transcriptomes generated under osmotic and oxidative stresses revealed up to 6% genes differentially expressed by at least twofold in the fungal genome. Many of those were greatly depressed or co‐depressed in Δ Bmh 1 and Δ Bmh 2 . Our findings provide a thorough insight into the functions and complementary effects of the two 14‐3‐3 proteins in the filamentous entomopathogen.

Expression of HMGB1 in the periodontal tissue subjected to orthodontic force application by Waldo’s method in mice - Shengyu Lv; Juan Li; Wei Feng; Hongrui Liu; Juan Du; Jing Sun; Jian Cui; Bao Sun; Xiuchun Han; Kimimitsu Oda; Norio Amizuka; Xin Xu; et al. (Journal of Molecular Histology, 2015)

Ground-dwelling arthropod community response to native grassland conversion in a temperate desert of northwestern China - Qi Feng; Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Li-Juan Chen (Journal of Insect Conservation, 2015)

Study of the genomic constitution of the German mirror carp - Ya-Juan Li; Bo Liu; He Zhou; Yang-Chun Gao; Min Gao; Yu-Sheng Wang; Ding-Chen Cao; Xiao-Wen Sun (Aquaculture International, 2015)

Knockdown of ANLN by lentivirus inhibits cell growth and migration in human breast cancer - Weibing Zhou; Zhan Wang; Ni Shen; Weiwei Pi; Wuzhong Jiang; Juan Huang; Yuanping Hu; Xiong Li; Lunquan Sun (Molecular and Cellular Biochemistry, 2015)

Identification of a novel mitogen-activated protein kinase kinase gene (MKK2) in the oilseed rape Brassica campestris - Teng Guo Zhang; Yuan Yuan Wang; Juan Wang; Xiao Hui Xia; Ning Yang; Ying Li Yang; Wan Cang Sun (Biologia, 2014)

Molecular cytogenetic study of genome ploidy in the German mirror carp Cyprinus carpio - Ya-Juan Li; Yang-Chun Gao; He Zhou; Bo Liu; Min Gao; Yu-Sheng Wang; Xiao-Wen Sun (Fisheries Science, 2014)

A pre-breeding screening program for transgenic boars based on fluorescence in situ hybridization assay - Gerelchimeg Bou; Mingju Sun; Ming Lv; Jiang Zhu; Hui Li; Juan Wang; Lu Li; Zhongfeng Liu; Zhong Zheng; Wenteng He; Qingran Kong; Zhonghua Liu (Transgenic Research, 2014)

Ectopic expression of Dendrobium EREB5 gene in Arabidopsis influences leaf morphology - Yuqiang Sun; Ying Shen; Anna Li; Wenfeng Fu; Yu Wang; Qicai Ying; Juan Hao; Brian Jones; Bo Shen; Huizhong Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Autophagy inhibitors promoted aristolochic acid I induced renal tubular epithelial cell apoptosis via mitochondrial pathway but alleviated nonapoptotic cell death in mouse acute aritolochic acid nephropathy model - Youjia Zeng; Shunmin Li; Juan Wu; Wenfang Chen; Huili Sun; Wenxing Peng; Xueqing Yu; Xiao Yang (Apoptosis, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Histochemical examination of cathepsin K, MMP1 and MMP2 in compressed periodontal ligament during orthodontic tooth movement in periostin deficient mice - Shengyu Lv; Hongrui Liu; Jian Cui; Tomoka Hasegawa; Hiromi Hongo; Wei Feng; Juan Li; Bao Sun; Akira Kudo; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Utilizing pyrene-degrading endophytic bacteria to reduce the risk of plant pyrene contamination - Kai Sun; Juan Liu; Li Jin; Yanzheng Gao (Plant and Soil, 2014)

Interleukin-18 promoter polymorphisms and plasma levels are associated with increased risk of periodontitis: a meta-analysis - Zhi-Gang Li; Jin-Juan Li; Chang-An Sun; Yuan Jin; Wei-Wei Wu (Inflammation Research, 2014)

Molecular cloning and characterization of the mitogen-activated protein kinase kinase gene (MKK4) and its promoter sequence from oilseed rape (Brassica campestris L.) - Teng Guo Zhang; Qiong Qiong Chen; Ning Wang; Xiao Hui Xia; Juan Wang; Yan Chang; Ying Li Yang; Ning Yang; Wan Cang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Coronary heart disease diagnosis bases on the change of different parts in treadmill exercise test ECG - Sun Jian-ling; Zhao Ying; Gao Yu-lian; Xiong Li-juan; Guo Ji-hong; Li Xiao-ying (Cell Biochemistry and Biophysics, 2013)

Elderly Patients and Coronary Heart Disease on Response to Treadmill Exercise Test - Jian-ling Sun; Guo-lan Gao; Ying Zhao; Yu-lian Gao; Li-juan Xiong; Ji-hong Guo; Xiao-ying Li (Cell Biochemistry and Biophysics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Targeted editing of goat genome with modular-assembly zinc finger nucleases based on activity prediction by computational molecular modeling - Kai Xiong; Shanshan Li; Hongxiao Zhang; Ye Cui; Debing Yu; Yan Li; Wenxing Sun; Yingying Fu; Yun Teng; Zhi Liu; Xiaolong Zhou; Peng Xiao; et al. (Molecular Biology Reports, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Effects of Formaldehyde Stress on Physiological Characteristics and Gene Expression Associated with Photosynthesis in Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Plant Molecular Biology Reporter, 2012)

Interactions of interleukin-12A and interleukin-12B polymorphisms on the risk of intracranial aneurysm - Li-Juan Li; Xin-Min Pan; Xiutian Sima; Zhao-Hui Li; Lu-Shun Zhang; Hong Sun; Yi Zhu; Wei-Bo Liang; Lin-Bo Gao; Lin Zhang (Molecular Biology Reports, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Methylation pattern of oncogene HRAS gene promoter region and its clinical relevance to urocystic tumorigenesis - Xiao-Feng Sun; Lan Li; Xiu-Juan Li; Wei Shen (Molecular Biology Reports, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Determination of 16 polycyclic aromatic hydrocarbons in water using fluorinated polyaniline-based solid-phase microextraction coupled with gas chromatography - Yongqiang Li; Yonghua Wang; Juan Zhang; Cheng Sun (Environmental Monitoring and Assessment, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Erratum to: Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

Physiological and transcriptional analysis of the effects of formaldehyde exposure on Arabidopsis thaliana - Sha-Sha Wang; Zhong-Bang Song; Zhen Sun; Jing Zhang; Yan Mei; Hong-Juan Nian; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

A New Method to Extract Matrix Proteins Directly from the Secretion of the Mollusk Mantle and the Role of These Proteins in Shell Biomineralization - Xiaojun Liu; Chang Liu; Lei Chen; Juan Sun; Yujuan Zhou; Qi Li; Guilan Zheng; Guiyou Zhang; Hongzhong Wang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2011)

An object-oriented daytime land-fog-detection approach based on the mean-shift and full lambda-schedule algorithms using EOS/MODIS data - Liangming Liu; Xiongfei Wen; Albano Gonzalez; Debao Tan; Juan Du; Yitong Liang; Wei Li; Dengke Fan; Kaimin Sun; Pei Dong; Daxiang Xiang; Zheng Zhou (International Journal of Remote Sensing, 2011)

Photocatalytic degradation of phenol with mesoporous TiO2−xBx - Leyan Xiong; Longzhen Zheng; Jingpeng Xu; Dan Zheng; Junhua Li; Xinjia Li; Juan Sun; Qiang Liu; Liling Niu; Shaoming Yang; Jian Xia (Environmental Chemistry Letters, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

Variabilities of Two Drechslerella dactyloides Isolates in Korea and High Predacity Against Bursaphelenchus xylophilus - Zhen Wang; Chun-Yan Wang; Li-Juan Gu; Bai-Shen Sun; Dong-Liang Zhang; Lei Liu; Mi-Ra Lee; Chun-Ling Wang; Zheng Li; Eun-Kyung Mo; Chang-Keun Sung (Current Microbiology, 2011)

Acetylcholine prevents angiotensin II-induced oxidative stress and apoptosis in H9c2 cells - Jin-Jun Liu; Dong-Ling Li; Juan Zhou; Lei Sun; Ming Zhao; Shan-Shan Kong; You-Hua Wang; Xiao-Jiang Yu; Jun Zhou; Wei-Jin Zang (Apoptosis, 2011)

Effects of oriented substrates on cell morphology, the cell cycle, and the cytoskeleton in Ros 17/2.8 cells - Hong Li; Juan Chen; Yan Zhang; ShuJin Sun; ZuLai Tao; Mian Long (Science China Life Sciences, 2010)

A Novel Cytoplasmic Isopentenyl Diphosphate Isomerase Gene from Tomato (Solanum lycopersicum): Cloning, Expression, and Color Complementation - Jin Sun; Yu-Yang Zhang; Hui Liu; Zhe Zou; Chan-Juan Zhang; Xiao-Hui Zhang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Synthesis and Luminescence Properties of Two Novel Lanthanide (III) Perchlorate Complexes with Bis(benzoylmethyl) Sulfoxide and Benzoic Acid - Wen-Xian Li; Wen-Juan Chai; Xiao-Jun Sun; Tie Ren; Xiao-Yan Shi (Journal of Fluorescence, 2010)

The Studies of Enhanced Fluorescence in the Two Novel Ternary Rare-Earth Complex Systems - Xiao-Jun Sun; Wen-Xian Li; Wen-Juan Chai; Tie Ren; Xiao-Yan Shi (Journal of Fluorescence, 2010)

Expression of the apoptosis-related proteins caspase-3 and NF-κB in the hippocampus of Tg2576 mice - Yan-Li Niu; Wei-Juan Zhang; Ping Wu; Bin Liu; Guo-Tao Sun; Dong-Ming Yu; Jin-Bo Deng (Neuroscience Bulletin, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Synthesis and Fluorescence Properties of Lanthanide (III) Perchlorate Complexes with Naphthyl-Naphthalinesulphonylpropyl Sulfoxide - Wen-Xian Li; Yu-Shan Zheng; Xiao-Jun Sun; Xiao-Yan Shi; Wen-Juan Chai; Tie Ren (Journal of Fluorescence, 2010)

Effects of Gestational Cadmium Exposure on Pregnancy Outcome and Development in the Offspring at Age 4.5 Years - Li-Li Tian; Yong-Cheng Zhao; Xiao-Chun Wang; Jin-Long Gu; Zhi-Juan Sun; Ya-Li Zhang; Ji-Xian Wang (Biological Trace Element Research, 2009)

POPs accumulated in fish and benthos bodies taken from Yangtze River in Jiangsu area - Guanjiu Hu; Cheng Sun; Juan Li; Yonggang Zhao; Hui Wang; Yiqiang Li (Ecotoxicology, 2009)

Turning Earthquake Disaster into Long‐Term Benefits for the Panda - DAJUN WANG; SHENG LI; SHAN SUN; HAO WANG; AI CHEN; SHENGZHI LI; JUAN LI; ZHI LU (Conservation Biology, 2008)

Use of herbicide-resistant genic male sterility in hybrid rice seed production - Sung Soo Kim; Jae Youn Jung; Seung Kwon Jeong; Dong Sun Lee; Li Juan Chen; Hak Soo Suh (Euphytica, 2007)

rAAV-mediated angiogenin gene transfer induces angiogenesis and modifies left ventricular remodeling in rats with myocardial infarction - Xiao-Yan Zhao; Shen-Jiang Hu; Jiang Li; Yun Mou; Chi-Fung Chan; Juan Jin; Jian Sun; Zhao-Hui Zhu (Journal of Molecular Medicine, 2006)

Genetic characterization and fine mapping of a novel thermo-sensitive genic male-sterile gene tms6 in rice (Oryza sativa L.) - Dong Sun Lee; Li Juan Chen; Hak Soo Suh (Theoretical and Applied Genetics, 2005)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)